New fluorescent auxin derivatives: anti-auxin activity and accumulation patterns in Arabidopsis thaliana - Bieleszová, Kristýna; Hladík, Pavel; Kubala, Martin; Napier, Richard; Brunoni, Federica; Gelová, Zuzana; Fiedler, Lukas; Kulich, Ivan; Strnad, Miroslav; Doležal, Karel; Novák, Ondřej; Friml, Jiří; et al. (Plant Growth Regulation)
Auxin belongs among major phytohormones and governs multiple aspects of plant growth and development. The establishment of auxin concentration gradients, determines, among other processes, plant organ positioning and growth responses to environmental stimuli. Herein we report the synthesis of new NBD- or DNS-labelled IAA derivatives and the elucidation of their biological activity, fluorescence properties and subcellular accumulation patterns in planta. These novel compounds did not show auxin-like activity, but instead antagonized physiological auxin effects. The DNS-labelled derivatives FL5 and FL6 showed strong anti-auxin activity in roots and hypocotyls, which also occurred at the level of gene transcription as confirmed by quantitative PCR analysis. The auxin antagonism of our derivatives was further demonstrated in vitro using an SPR-based binding assay. The NBD-labelled compound FL4 with the best fluorescence properties proved to be unsuitable to study auxin accumulation patterns in planta. On the other hand, the strongest anti-auxin activity possessing compounds FL5 and FL6 could be useful to study binding mechanisms to auxin receptors and for manipulations of auxin-regulated processes.

Improving variational quantum algorithms: Innovative initialization techniques and extensions to qudit systems - Sack, Stefan

Protocol for sorting cells from mouse brains labeled with mosaic analysis with double markers by flow cytometry - Amberg, Nicole; Cheung, Giselle T; Hippenmeyer, Simon (STAR Protocols)
Mosaic analysis with double markers (MADM) technology enables the generation of genetic mosaic tissue in mice and high-resolution phenotyping at the individual cell level. Here, we present a protocol for isolating MADM-labeled cells with high yield for downstream molecular analyses using fluorescence-activated cell sorting (FACS). We describe steps for generating MADM-labeled mice, perfusion, single-cell suspension, and debris removal. We then detail procedures for cell sorting by FACS and downstream analysis. This protocol is suitable for embryonic to adult mice. For complete details on the use and execution of this protocol, please refer to Contreras et al. (2021).1
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Neuroscience

Delayed blow-up and enhanced diffusion by transport noise for systems of reaction-diffusion equations - Agresti, Antonio (Stochastics and Partial Differential Equations: Analysis and Computations)
This paper is concerned with the problem of regularization by noise of systems of reaction–diffusion equations with mass control. It is known that strong solutions to such systems of PDEs may blow-up in finite time. Moreover, for many systems of practical interest, establishing whether the blow-up occurs or not is an open question. Here we prove that a suitable multiplicative noise of transport type has a regularizing effect. More precisely, for both a sufficiently noise intensity and a high spectrum, the blow-up of strong solutions is delayed up to an arbitrary large time. Global existence is shown for the case of exponentially decreasing mass. The proofs combine and extend recent developments in regularization by noise and in the Lp(Lq)-approach to stochastic PDEs, highlighting new connections between the two areas.

Multiple packing: Lower bounds via error exponents - Zhang, Yihan; Vatedka, Shashank (IEEE Transactions on Information Theory)
We derive lower bounds on the maximal rates for multiple packings in high-dimensional Euclidean spaces. For any N > 0 and L ∈ Z ≥2 , a multiple packing is a set C of points in R n such that any point in R n lies in the intersection of at most L - 1 balls of radius √ nN around points in C . This is a natural generalization of the sphere packing problem. We study the multiple packing problem for both bounded point sets whose points have norm at most √ nP for some constant P > 0, and unbounded point sets whose points are allowed to be anywhere in R n . Given a well-known connection with coding theory, multiple packings can be viewed as the Euclidean analog of list-decodable codes, which are well-studied over finite fields. We derive the best known lower bounds on the optimal multiple packing density. This is accomplished by establishing an inequality which relates the list-decoding error exponent for additive white Gaussian noise channels, a quantity of average-case nature, to the list-decoding radius, a quantity of worst-case nature. We also derive novel bounds on the list-decoding error exponent for infinite constellations and closed-form expressions for the list-decoding error exponents for the power-constrained AWGN channel, which may be of independent interest beyond multiple packing.

(Verifiable) delay functions from Lucas sequences - Hoffmann, Charlotte; Hubáček, Pavel; Kamath, Chethan; Krňák, Tomáš (21st International Conference on Theory of Cryptography)
Lucas sequences are constant-recursive integer sequences with a long history of applications in cryptography, both in the design of cryptographic schemes and cryptanalysis. In this work, we study the sequential hardness of computing Lucas sequences over an RSA modulus. First, we show that modular Lucas sequences are at least as sequentially hard as the classical delay function given by iterated modular squaring proposed by Rivest, Shamir, and Wagner (MIT Tech. Rep. 1996) in the context of time-lock puzzles. Moreover, there is no obvious reduction in the other direction, which suggests that the assumption of sequential hardness of modular Lucas sequences is strictly weaker than that of iterated modular squaring. In other words, the sequential hardness of modular Lucas sequences might hold even in the case of an algorithmic improvement violating the sequential hardness of iterated modular squaring. Second, we demonstrate the feasibility of constructing practically-efficient verifiable delay functions based on the sequential hardness of modular Lucas sequences. Our construction builds on the work of Pietrzak (ITCS 2019) by leveraging the intrinsic connection between the problem of computing modular Lucas sequences and exponentiation in an appropriate extension field.

On the cost of post-compromise security in concurrent Continuous Group-Key Agreement - Auerbach, Benedikt; Cueto Noval, Miguel; Pascual Perez, Guillermo; Pietrzak, Krzysztof Z (21st International Conference on Theory of Cryptography)
Continuous Group-Key Agreement (CGKA) allows a group of users to maintain a shared key. It is the fundamental cryptographic primitive underlying group messaging schemes and related protocols, most notably TreeKEM, the underlying key agreement protocol of the Messaging Layer Security (MLS) protocol, a standard for group messaging by the IETF. CKGA works in an asynchronous setting where parties only occasionally must come online, and their messages are relayed by an untrusted server. The most expensive operation provided by CKGA is that which allows for a user to refresh their key material in order to achieve forward secrecy (old messages are secure when a user is compromised) and post-compromise security (users can heal from compromise). One caveat of early CGKA protocols is that these update operations had to be performed sequentially, with any user wanting to update their key material having had to receive and process all previous updates. Late versions of TreeKEM do allow for concurrent updates at the cost of a communication overhead per update message that is linear in the number of updating parties. This was shown to be indeed necessary when achieving PCS in just two rounds of communication by [Bienstock et al. TCC’20]. The recently proposed protocol CoCoA [Alwen et al. Eurocrypt’22], however, shows that this overhead can be reduced if PCS requirements are relaxed, and only a logarithmic number of rounds is required. The natural question, thus, is whether CoCoA is optimal in this setting. In this work we answer this question, providing a lower bound on the cost (concretely, the amount of data to be uploaded to the server) for CGKA protocols that heal in an arbitrary k number of rounds, that shows that CoCoA is very close to optimal. Additionally, we extend CoCoA to heal in an arbitrary number of rounds, and propose a modification of it, with a reduced communication cost for certain k. We prove our bound in a combinatorial setting where the state of the protocol progresses in rounds, and the state of the protocol in each round is captured by a set system, each set specifying a set of users who share a secret key. We show this combinatorial model is equivalent to a symbolic model capturing building blocks including PRFs and public-key encryption, related to the one used by Bienstock et al. Our lower bound is of order k•n1+1/(k-1)/log(k), where 2≤k≤log(n) is the number of updates per user the protocol requires to heal. This generalizes the n2 bound for k=2 from Bienstock et al.. This bound almost matches the k⋅n1+2/(k-1) or k2⋅n1+1/(k-1) efficiency we get for the variants of the CoCoA protocol also introduced in this paper.

Generic-group lower bounds via reductions between geometric-search problems: With and without preprocessing - Auerbach, Benedikt; Hoffmann, Charlotte; Pascual Perez, Guillermo (21st International Conference on Theory of Cryptography)
The generic-group model (GGM) aims to capture algorithms working over groups of prime order that only rely on the group operation, but do not exploit any additional structure given by the concrete implementation of the group. In it, it is possible to prove information-theoretic lower bounds on the hardness of problems like the discrete logarithm (DL) or computational Diffie-Hellman (CDH). Thus, since its introduction, it has served as a valuable tool to assess the concrete security provided by cryptographic schemes based on such problems. A work on the related algebraic-group model (AGM) introduced a method, used by many subsequent works, to adapt GGM lower bounds for one problem to another, by means of conceptually simple reductions. In this work, we propose an alternative approach to extend GGM bounds from one problem to another. Following an idea by Yun [EC15], we show that, in the GGM, the security of a large class of problems can be reduced to that of geometric search-problems. By reducing the security of the resulting geometric-search problems to variants of the search-by-hypersurface problem, for which information theoretic lower bounds exist, we give alternative proofs of several results that used the AGM approach. The main advantage of our approach is that our reduction from geometric search-problems works, as well, for the GGM with preprocessing (more precisely the bit-fixing GGM introduced by Coretti, Dodis and Guo [Crypto18]). As a consequence, this opens up the possibility of transferring preprocessing GGM bounds from one problem to another, also by means of simple reductions. Concretely, we prove novel preprocessing bounds on the hardness of the d-strong discrete logarithm, the d-strong Diffie-Hellman inversion, and multi-instance CDH problems, as well as a large class of Uber assumptions. Additionally, our approach applies to Shoup’s GGM without additional restrictions on the query behavior of the adversary, while the recent works of Zhang, Zhou, and Katz [AC22] and Zhandry [Crypto22] highlight that this is not the case for the AGM approach.

Boundary multifractality in the spin quantum Hall symmetry class with interaction - Babkin, Serafim; Burmistrov, I (Physical Review B)
Generalized multifractality characterizes system size dependence of pure scaling local observables at Anderson transitions in all 10 symmetry classes of disordered systems. Recently, the concept of generalized multifractality has been extended to boundaries of critical disordered noninteracting systems. Here we study the generalized boundary multifractality in the presence of electron-electron interaction, focusing on the spin quantum Hall symmetry class (class C). Employing the two-loop renormalization group analysis within the Finkel'stein nonlinear sigma model, we compute the anomalous dimensions of the pure scaling operators located at the boundary of the system. We find that generalized boundary multifractal exponents are twice larger than their bulk counterparts. Exact symmetry relations between generalized boundary multifractal exponents in the case of noninteracting systems are explicitly broken by the interaction.

Reply to: Revisiting the use of structural similarity index in Hi-C - Ing-Simmons, Elizabeth; Machnik, Nick N; Vaquerizas, Juan M. (Nature Genetics)

Towards practical metal–oxygen batteries: General discussion - Archer, Lynden A.; Bruce, Peter G.; Calvo, Ernesto J.; Dewar, Daniel; Ellison, James H. J.; Freunberger, Stefan Alexander; Gao, Xiangwen; Hardwick, Laurence J.; Horwitz, Gabriela; Janek, Jürgen; Johnson, Lee R.; Jordan, Jack W.; et al. (Faraday Discussions)
Keywords: Physical and Theoretical Chemistry

Materials for stable metal–oxygen battery cathodes: general discussion - Attard, Gary A.; Calvo, Ernesto J.; Curtiss, Larry A.; Dewar, Daniel; Ellison, James H. J.; Gao, Xiangwen; Grey, Clare P.; Hardwick, Laurence J.; Horwitz, Gabriela; Janek, Juergen; Johnson, Lee R.; Jordan, Jack W.; et al. (Faraday Discussions)
Keywords: Physical and Theoretical Chemistry

Sensing their plasma membrane curvature allows migrating cells to circumvent obstacles - Sitarska, Ewa; Almeida, Silvia Dias; Beckwith, Marianne Sandvold; Stopp, Julian A; Czuchnowski, Jakub; Siggel, Marc; Roessner, Rita; Tschanz, Aline; Ejsing, Christer; Schwab, Yannick; Kosinski, Jan; Sixt, Michael K; et al. (Nature Communications)
To navigate through diverse tissues, migrating cells must balance persistent self-propelled motion with adaptive behaviors to circumvent obstacles. We identify a curvature-sensing mechanism underlying obstacle evasion in immune-like cells. Specifically, we propose that actin polymerization at the advancing edge of migrating cells is inhibited by the curvature-sensitive BAR domain protein Snx33 in regions with inward plasma membrane curvature. The genetic perturbation of this machinery reduces the cells’ capacity to evade obstructions combined with faster and more persistent cell migration in obstacle-free environments. Our results show how cells can read out their surface topography and utilize actin and plasma membrane biophysics to interpret their environment, allowing them to adaptively decide if they should move ahead or turn away. On the basis of our findings, we propose that the natural diversity of BAR domain proteins may allow cells to tune their curvature sensing machinery to match the shape characteristics in their environment.

CCR7 acts as both a sensor and a sink for CCL19 to coordinate collective leukocyte migration - Alanko, Jonna H; Ucar, Mehmet C; Canigova, Nikola; Stopp, Julian A; Schwarz, Jan; Merrin, Jack; Hannezo, Edouard B; Sixt, Michael K (Science Immunology)
Immune responses rely on the rapid and coordinated migration of leukocytes. Whereas it is well established that single-cell migration is often guided by gradients of chemokines and other chemoattractants, it remains poorly understood how these gradients are generated, maintained, and modulated. By combining experimental data with theory on leukocyte chemotaxis guided by the G protein–coupled receptor (GPCR) CCR7, we demonstrate that in addition to its role as the sensory receptor that steers migration, CCR7 also acts as a generator and a modulator of chemotactic gradients. Upon exposure to the CCR7 ligand CCL19, dendritic cells (DCs) effectively internalize the receptor and ligand as part of the canonical GPCR desensitization response. We show that CCR7 internalization also acts as an effective sink for the chemoattractant, dynamically shaping the spatiotemporal distribution of the chemokine. This mechanism drives complex collective migration patterns, enabling DCs to create or sharpen chemotactic gradients. We further show that these self-generated gradients can sustain the long-range guidance of DCs, adapt collective migration patterns to the size and geometry of the environment, and provide a guidance cue for other comigrating cells. Such a dual role of CCR7 as a GPCR that both senses and consumes its ligand can thus provide a novel mode of cellular self-organization.
Keywords: General Medicine; Immunology

Neutrophils on the hunt: Migratory strategies employed by neutrophils to fulfill their effector function - Stopp, Julian A

Investigating inbreeding depression and the self-incompatibility locus of Antirrhinum majus - Arathoon, Louise S
For self-incompatibility (SI) to be stable in a population, theory predicts that sufficient inbreeding depression (ID) is required: the fitness of offspring from self-mated individuals must be low enough to prevent the spread of self-compatibility (SC). Reviews of natural plant populations have supported this theory, with SI species generally showing high levels of ID. However, there is thought to be an under-sampling of self-incompatible taxa in the current literature. In this thesis, I study inbreeding depression in the SI plant species Antirrhinum majus using both greenhouse crosses and a large collected field dataset. Additionally, the gametophytic S-locus of A. majus is highly heterozygous and polymorphic, thus making assembly and discovery of S-alleles very difficult. Here, 206 new alleles of the male component SLFs are presented, along with a phylogeny showing the high conservation with alleles from another Antirrhinum species. Lastly, selected sites within the protein structure of SLFs are investigated, with one site in particular highlighted as potentially being involved in the SI recognition mechanism.

Quantitative convergence of a discretization of dynamic optimal transport using the dual formulation - Ishida, Sadashige; Lavenant, Hugo (arXiv)
We present a discretization of the dynamic optimal transport problem for which we can obtain the convergence rate for the value of the transport cost to its continuous value when the temporal and spatial stepsize vanish. This convergence result does not require any regularity assumption on the measures, though experiments suggest that the rate is not sharp. Via an analysis of the duality gap we also obtain the convergence rates for the gradient of the optimal potentials and the velocity field under mild regularity assumptions. To obtain such rates we discretize the dual formulation of the dynamic optimal transport problem and use the mature literature related to the error due to discretizing the Hamilton-Jacobi equation.
Keywords: Optimal transport; Hamilton-Jacobi equation; convex optimization

Machine learning and phylogenetic analysis allow for predicting antibiotic resistance in M. tuberculosis - Yurtseven, Alper; Buyanova, Sofia; Agrawal, Amay Ajaykumar A.; Bochkareva, Olga; Kalinina, Olga V V. (BMC Microbiology)
Background: Antimicrobial resistance (AMR) poses a significant global health threat, and an accurate prediction of bacterial resistance patterns is critical for effective treatment and control strategies. In recent years, machine learning (ML) approaches have emerged as powerful tools for analyzing large-scale bacterial AMR data. However, ML methods often ignore evolutionary relationships among bacterial strains, which can greatly impact performance of the ML methods, especially if resistance-associated features are attempted to be detected. Genome-wide association studies (GWAS) methods like linear mixed models accounts for the evolutionary relationships in bacteria, but they uncover only highly significant variants which have already been reported in literature. Results: In this work, we introduce a novel phylogeny-related parallelism score (PRPS), which measures whether a certain feature is correlated with the population structure of a set of samples. We demonstrate that PRPS can be used, in combination with SVM- and random forest-based models, to reduce the number of features in the analysis, while simultaneously increasing models’ performance. We applied our pipeline to publicly available AMR data from PATRIC database for Mycobacterium tuberculosis against six common antibiotics. Conclusions: Using our pipeline, we re-discovered known resistance-associated mutations as well as new candidate mutations which can be related to resistance and not previously reported in the literature. We demonstrated that taking into account phylogenetic relationships not only improves the model performance, but also yields more biologically relevant predicted most contributing resistance markers.

Binary decision diagrams on modern hardware - Pastva, Samuel; Henzinger, Thomas A (Proceedings of the 23rd Conference on Formal Methods in Computer-Aided Design)
Binary decision diagrams (BDDs) are one of the fundamental data structures in formal methods and computer science in general. However, the performance of BDD-based algorithms greatly depends on memory latency due to the reliance on large hash tables and thus, by extension, on the speed of random memory access. This hinders the full utilisation of resources available on modern CPUs, since the absolute memory latency has not improved significantly for at least a decade. In this paper, we explore several implementation techniques that improve the performance of BDD manipulation either through enhanced memory locality or by partially eliminating random memory access. On a benchmark suite of 600+ BDDs derived from real-world applications, we demonstrate runtime that is comparable or better than parallelising the same operations on eight CPU cores.

Equidistribution of primitive lattices in ℝn - Horesh, Tal; Karasik, Yakov (Quarterly Journal of Mathematics)
We count primitive lattices of rank d inside Zn as their covolume tends to infinity, with respect to certain parameters of such lattices. These parameters include, for example, the subspace that a lattice spans, namely its projection to the Grassmannian; its homothety class and its equivalence class modulo rescaling and rotation, often referred to as a shape. We add to a prior work of Schmidt by allowing sets in the spaces of parameters that are general enough to conclude the joint equidistribution of these parameters. In addition to the primitive d-lattices Λ themselves, we also consider their orthogonal complements in Zn⁠, A1⁠, and show that the equidistribution occurs jointly for Λ and A1⁠. Finally, our asymptotic formulas for the number of primitive lattices include an explicit bound on the error term.

Nanostructured Li₂S cathodes for silicon-sulfur batteries - Mollania, Hamid; Zhang, Chaoqi; Du, Ruifeng; Qi, Xueqiang; Li, Junshan; Horta, Sharona; Ibáñez, Maria; Keller, Caroline; Chenevier, Pascale; Oloomi-Buygi, Majid; Cabot, Andreu (ACS Applied Materials and Interfaces)
Lithium–sulfur batteries are regarded as an advantageous option for meeting the growing demand for high-energy-density storage, but their commercialization relies on solving the current limitations of both sulfur cathodes and lithium metal anodes. In this scenario, the implementation of lithium sulfide (Li2S) cathodes compatible with alternative anode materials such as silicon has the potential to alleviate the safety concerns associated with lithium metal. In this direction, here, we report a sulfur cathode based on Li2S nanocrystals grown on a catalytic host consisting of CoFeP nanoparticles supported on tubular carbon nitride. Nanosized Li2S is incorporated into the host by a scalable liquid infiltration–evaporation method. Theoretical calculations and experimental results demonstrate that the CoFeP–CN composite can boost the polysulfide adsorption/conversion reaction kinetics and strongly reduce the initial overpotential activation barrier by stretching the Li–S bonds of Li2S. Besides, the ultrasmall size of the Li2S particles in the Li2S–CoFeP–CN composite cathode facilitates the initial activation. Overall, the Li2S–CoFeP–CN electrodes exhibit a low activation barrier of 2.56 V, a high initial capacity of 991 mA h gLi2S–1, and outstanding cyclability with a small fading rate of 0.029% per cycle over 800 cycles. Moreover, Si/Li2S full cells are assembled using the nanostructured Li2S–CoFeP–CN cathode and a prelithiated anode based on graphite-supported silicon nanowires. These Si/Li2S cells demonstrate high initial discharge capacities above 900 mA h gLi2S–1 and good cyclability with a capacity fading rate of 0.28% per cycle over 150 cycles.

Exponential decay of the number of excitations in the weakly interacting Bose gas - Mitrouskas, David Johannes; Pickl, Peter (Journal of Mathematical Physics)
We consider N trapped bosons in the mean-field limit with coupling constant λN = 1/(N − 1). The ground state of such systems exhibits Bose–Einstein condensation. We prove that the probability of finding ℓ particles outside the condensate wave function decays exponentially in ℓ.

Generalizing shallow water simulations with dispersive surface waves - Jeschke, Stefan; Wojtan, Christopher J (ACM Transactions on Graphics)
This paper introduces a novel method for simulating large bodies of water as a height field. At the start of each time step, we partition the waves into a bulk flow (which approximately satisfies the assumptions of the shallow water equations) and surface waves (which approximately satisfy the assumptions of Airy wave theory). We then solve the two wave regimes separately using appropriate state-of-the-art techniques, and re-combine the resulting wave velocities at the end of each step. This strategy leads to the first heightfield wave model capable of simulating complex interactions between both deep and shallow water effects, like the waves from a boat wake sloshing up onto a beach, or a dam break producing wave interference patterns and eddies. We also analyze the numerical dispersion created by our method and derive an exact correction factor for waves at a constant water depth, giving us a numerically perfect re-creation of theoretical water wave dispersion patterns.

A computational toolbox for the assembly yield of complex and heterogeneous structures - Curatolo, Agnese I.; Kimchi, Ofer; Goodrich, Carl Peter; Krueger, Ryan K.; Brenner, Michael P. (Nature Communications)
The self-assembly of complex structures from a set of non-identical building blocks is a hallmark of soft matter and biological systems, including protein complexes, colloidal clusters, and DNA-based assemblies. Predicting the dependence of the equilibrium assembly yield on the concentrations and interaction energies of building blocks is highly challenging, owing to the difficulty of computing the entropic contributions to the free energy of the many structures that compete with the ground state configuration. While these calculations yield well known results for spherically symmetric building blocks, they do not hold when the building blocks have internal rotational degrees of freedom. Here we present an approach for solving this problem that works with arbitrary building blocks, including proteins with known structure and complex colloidal building blocks. Our algorithm combines classical statistical mechanics with recently developed computational tools for automatic differentiation. Automatic differentiation allows efficient evaluation of equilibrium averages over configurations that would otherwise be intractable. We demonstrate the validity of our framework by comparison to molecular dynamics simulations of simple examples, and apply it to calculate the yield curves for known protein complexes and for the assembly of colloidal shells.

Auxin research: Creating tools for a greener future - Del Bianco, Marta; Friml, Jiří; Strader, Lucia; Kepinski, Stefan (Journal of Experimental Botany)
Amid the delays due to the global pandemic, in early October 2022, the auxin community gathered in the idyllic peninsula of Cavtat, Croatia. More than 170 scientists from across the world converged to discuss the latest advancements in fundamental and applied research in the field. The topics, from signalling and transport to plant architecture and response to the environment, show how auxin research must bridge from the molecular realm to macroscopic developmental responses. This is mirrored in this collection of reviews, contributed by participants of the Auxin 2022 meeting.

Token swapping on trees - Biniaz, Ahmad; Jain, Kshitij; Lubiw, Anna; Masárová, Zuzana; Miltzow, Tillmann; Mondal, Debajyoti; Naredla, Anurag Murty; Tkadlec, Josef; Turcotte, Alexi (Discrete Mathematics and Theoretical Computer Science)
The input to the token swapping problem is a graph with vertices v1, v2, . . . , vn, and n tokens with labels 1,2, . . . , n, one on each vertex. The goal is to get token i to vertex vi for all i= 1, . . . , n using a minimum number of swaps, where a swap exchanges the tokens on the endpoints of an edge.Token swapping on a tree, also known as “sorting with a transposition tree,” is not known to be in P nor NP-complete. We present some partial results: 1. An optimum swap sequence may need to perform a swap on a leaf vertex that has the correct token (a “happy leaf”), disproving a conjecture of Vaughan. 2. Any algorithm that fixes happy leaves—as all known approximation algorithms for the problem do—has approximation factor at least 4/3. Furthermore, the two best-known 2-approximation algorithms have approximation factor exactly 2. 3. A generalized problem—weighted coloured token swapping—is NP-complete on trees, but solvable in polynomial time on paths and stars. In this version, tokens and vertices have colours, and colours have weights. The goal is to get every token to a vertex of the same colour, and the cost of a swap is the sum of the weights of the two tokens involved.

Executing and proving over dirty ledgers - Stefo, Christos; Xiang, Zhuolun; Kokoris Kogias, Eleftherios (27th International Conference on Financial Cryptography and Data Security)
Scaling blockchain protocols to perform on par with the expected needs of Web3.0 has been proven to be a challenging task with almost a decade of research. In the forefront of the current solution is the idea of separating the execution of the updates encoded in a block from the ordering of blocks. In order to achieve this, a new class of protocols called rollups has emerged. Rollups have as input a total ordering of valid and invalid transactions and as output a new valid state-transition. If we study rollups from a distributed computing perspective, we uncover that rollups take as input the output of a Byzantine Atomic Broadcast (BAB) protocol and convert it to a State Machine Replication (SMR) protocol. BAB and SMR, however, are considered equivalent as far as distributed computing is concerned and a solution to one can easily be retrofitted to solve the other simply by adding/removing an execution step before the validation of the input. This “easy” step of retrofitting an atomic broadcast solution to implement an SMR has, however, been overlooked in practice. In this paper, we formalize the problem and show that after BAB is solved, traditional impossibility results for consensus no longer apply towards an SMR. Leveraging this we propose a distributed execution protocol that allows reduced execution and storage cost per executor (O(log2n/n)) without relaxing the network assumptions of the underlying BAB protocol and providing censorship-resistance. Finally, we propose efficient non-interactive light client constructions that leverage our efficient execution protocols and do not require any synchrony assumptions or expensive ZK-proofs.

Exploring the landscape of heterocyclic quinones for redox flow batteries - Jethwa, Rajesh B; Hey, Dominic; Kerber, Rachel N.; Bond, Andrew D.; Wright, Dominic S.; Grey, Clare P. (ACS Applied Energy Materials)
Redox flow batteries (RFBs) rely on the development of cheap, highly soluble, and high-energy-density electrolytes. Several candidate quinones have already been investigated in the literature as two-electron anolytes or catholytes, benefiting from fast kinetics, high tunability, and low cost. Here, an investigation of nitrogen-rich fused heteroaromatic quinones was carried out to explore avenues for electrolyte development. These quinones were synthesized and screened by using electrochemical techniques. The most promising candidate, 4,8-dioxo-4,8-dihydrobenzo[1,2-d:4,5-d′]bis([1,2,3]triazole)-1,5-diide (−0.68 V(SHE)), was tested in both an asymmetric and symmetric full-cell setup resulting in capacity fade rates of 0.35% per cycle and 0.0124% per cycle, respectively. In situ ultraviolet-visible spectroscopy (UV–Vis), nuclear magnetic resonance (NMR), and electron paramagnetic resonance (EPR) spectroscopies were used to investigate the electrochemical stability of the charged species during operation. UV–Vis spectroscopy, supported by density functional theory (DFT) modeling, reaffirmed that the two-step charging mechanism observed during battery operation consisted of two, single-electron transfers. The radical concentration during battery operation and the degree of delocalization of the unpaired electron were quantified with NMR and EPR spectroscopy.
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Electrochemistry; Energy Engineering and Power Technology; Chemical Engineering (miscellaneous)

Band engineering through Pb-doping of nanocrystal building blocks to enhance thermoelectric performance in Cu3SbSe4 - Wan, Shanhong; Xiao, Shanshan; Li, Mingquan; Wang, Xin; Lim, Khak Ho; Hong, Min; Ibáñez, Maria; Cabot, Andreu; Liu, Yu (Small Methods)
Developing cost-effective and high-performance thermoelectric (TE) materials to assemble efficient TE devices presents a multitude of challenges and opportunities. Cu3SbSe4 is a promising p-type TE material based on relatively earth abundant elements. However, the challenge lies in its poor electrical conductivity. Herein, an efficient and scalable solution-based approach is developed to synthesize high-quality Cu3SbSe4 nanocrystals doped with Pb at the Sb site. After ligand displacement and annealing treatments, the dried powders are consolidated into dense pellets, and their TE properties are investigated. Pb doping effectively increases the charge carrier concentration, resulting in a significant increase in electrical conductivity, while the Seebeck coefficients remain consistently high. The calculated band structure shows that Pb doping induces band convergence, thereby increasing the effective mass. Furthermore, the large ionic radius of Pb2+ results in the generation of additional point and plane defects and interphases, dramatically enhancing phonon scattering, which significantly decreases the lattice thermal conductivity at high temperatures. Overall, a maximum figure of merit (zTmax) ≈ 0.85 at 653 K is obtained in Cu3Sb0.97Pb0.03Se4. This represents a 1.6-fold increase compared to the undoped sample and exceeds most doped Cu3SbSe4-based materials produced by solid-state, demonstrating advantages of versatility and cost-effectiveness using a solution-based technology.

Functional John and Löwner conditions for pairs of log-concave functions - Ivanov, Grigory; Naszódi, Márton (International Mathematics Research Notices)
John’s fundamental theorem characterizing the largest volume ellipsoid contained in a convex body $K$ in $\mathbb{R}^{d}$ has seen several generalizations and extensions. One direction, initiated by V. Milman is to replace ellipsoids by positions (affine images) of another body $L$. Another, more recent direction is to consider logarithmically concave functions on $\mathbb{R}^{d}$ instead of convex bodies: we designate some special, radially symmetric log-concave function $g$ as the analogue of the Euclidean ball, and want to find its largest integral position under the constraint that it is pointwise below some given log-concave function $f$. We follow both directions simultaneously: we consider the functional question, and allow essentially any meaningful function to play the role of $g$ above. Our general theorems jointly extend known results in both directions. The dual problem in the setting of convex bodies asks for the smallest volume ellipsoid, called Löwner’s ellipsoid, containing $K$. We consider the analogous problem for functions: we characterize the solutions of the optimization problem of finding a smallest integral position of some log-concave function $g$ under the constraint that it is pointwise above $f$. It turns out that in the functional setting, the relationship between the John and the Löwner problems is more intricate than it is in the setting of convex bodies.
Keywords: General Mathematics

R2: Boosting liquidity in payment channel networks with online admission control - Bastankhah, Mahsa; Chatterjee, Krishnendu; Maddah-Ali, Mohammad Ali; Schmid, Stefan; Svoboda, Jakub; Yeo, Michelle X (27th International Conference on Financial Cryptography and Data Security)
Payment channel networks (PCNs) are a promising technology to improve the scalability of cryptocurrencies. PCNs, however, face the challenge that the frequent usage of certain routes may deplete channels in one direction, and hence prevent further transactions. In order to reap the full potential of PCNs, recharging and rebalancing mechanisms are required to provision channels, as well as an admission control logic to decide which transactions to reject in case capacity is insufficient. This paper presents a formal model of this optimisation problem. In particular, we consider an online algorithms perspective, where transactions arrive over time in an unpredictable manner. Our main contributions are competitive online algorithms which come with provable guarantees over time. We empirically evaluate our algorithms on randomly generated transactions to compare the average performance of our algorithms to our theoretical bounds. We also show how this model and approach differs from related problems in classic communication networks.

A survey of vectorization methods in topological data analysis - Ali, Dashti; Asaad, Aras; Jimenez, Maria-Jose; Nanda, Vidit; Paluzo-Hidalgo, Eduardo; Soriano Trigueros, Manuel (IEEE Transactions on Pattern Analysis and Machine Intelligence)
Attempts to incorporate topological information in supervised learning tasks have resulted in the creation of several techniques for vectorizing persistent homology barcodes. In this paper, we study thirteen such methods. Besides describing an organizational framework for these methods, we comprehensively benchmark them against three well-known classification tasks. Surprisingly, we discover that the best-performing method is a simple vectorization, which consists only of a few elementary summary statistics. Finally, we provide a convenient web application which has been designed to facilitate exploration and experimentation with various vectorization methods.
Keywords: Applied Mathematics; Artificial Intelligence; Computational Theory and Mathematics; Computer Vision and Pattern Recognition; Software

The impact of chromosomal rearrangements in speciation: From micro- to macroevolution - Lucek, Kay; Giménez, Mabel D.; Joron, Mathieu; Rafajlović, Marina; Searle, Jeremy B.; Walden, Nora; Westram, Anja M; Faria, Rui (Cold Spring Harbor Perspectives in Biology)
Chromosomal rearrangements (CRs) have been known since almost the beginning of genetics. While an important role for CRs in speciation has been suggested, evidence primarily stems from theoretical and empirical studies focusing on the microevolutionary level (i.e., on taxon pairs where speciation is often incomplete). Although the role of CRs in eukaryotic speciation at a macroevolutionary level has been supported by associations between species diversity and rates of evolution of CRs across phylogenies, these findings are limited to a restricted range of CRs and taxa. Now that more broadly applicable and precise CR detection approaches have become available, we address the challenges in filling some of the conceptual and empirical gaps between micro- and macroevolutionary studies on the role of CRs in speciation. We synthesize what is known about the macroevolutionary impact of CRs and suggest new research avenues to overcome the pitfalls of previous studies to gain a more comprehensive understanding of the evolutionary significance of CRs in speciation across the tree of life.
Keywords: General Biochemistry; Genetics and Molecular Biology

Divide & Scale: Formalization and roadmap to robust sharding - Avarikioti, Zeta; Desjardins, Antoine; Kokoris Kogias, Eleftherios; Wattenhofer, Roger (30th International Colloquium on Structural Information and Communication Complexity)
Sharding distributed ledgers is a promising on-chain solution for scaling blockchains but lacks formal grounds, nurturing skepticism on whether such complex systems can scale blockchains securely. We fill this gap by introducing the first formal framework as well as a roadmap to robust sharding. In particular, we first define the properties sharded distributed ledgers should fulfill. We build upon and extend the Bitcoin backbone protocol by defining consistency and scalability. Consistency encompasses the need for atomic execution of cross-shard transactions to preserve safety, whereas scalability encapsulates the speedup a sharded system can gain in comparison to a non-sharded system. Using our model, we explore the limitations of sharding. We show that a sharded ledger with n participants cannot scale under a fully adaptive adversary, but it can scale up to m shards where n=c'm log m, under an epoch-adaptive adversary; the constant c' encompasses the trade-off between security and scalability. This is possible only if the sharded ledgers create succinct proofs of the valid state updates at every epoch. We leverage our results to identify the sufficient components for robust sharding, which we incorporate in a protocol abstraction termed Divide & Scale. To demonstrate the power of our framework, we analyze the most prominent sharded blockchains (Elastico, Monoxide, OmniLedger, RapidChain) and pinpoint where they fail to meet the desired properties.

Monitoring and active stabilization of laser injection locking using beam ellipticity - Mishra, Umang; Li, Vyacheslav; Wald, Sebastian; Agafonova, Sofya; Diorico, Fritz R; Hosten, Onur (Optics Letters)
We unveil a powerful method for the stabilization of laser injection locking based on sensing variations in the output beam ellipticity of an optically seeded laser. The effect arises due to an interference between the seeding beam and the injected laser output. We demonstrate the method for a commercial semiconductor laser without the need for any internal changes to the readily operational injection locked laser system that was used. The method can also be used to increase the mode-hop free tuning range of lasers, and has the potential to fill a void in the low-noise laser industry.
Keywords: Atomic and Molecular Physics; and Optics

How moisture shapes low‐level radiative cooling in subsidence regimes - Fildier, B.; Muller, Caroline J; Pincus, R.; Fueglistaler, S. (AGU Advances)
Radiative cooling of the lowest atmospheric levels is of strong importance for modulating atmospheric circulations and organizing convection, but detailed observations and a robust theoretical understanding are lacking. Here we use unprecedented observational constraints from subsidence regimes in the tropical Atlantic to develop a theory for the shape and magnitude of low‐level longwave radiative cooling in clear‐sky, showing peaks larger than 5–10 K/day at the top of the boundary layer. A suite of novel scaling approximations is first developed from simplified spectral theory, in close agreement with the measurements. The radiative cooling peak height is set by the maximum lapse rate in water vapor path, and its magnitude is mainly controlled by the ratio of column relative humidity above and below the peak. We emphasize how elevated intrusions of moist air can reduce low‐level cooling, by sporadically shading the spectral range which effectively cools to space. The efficiency of this spectral shading depends both on water content and altitude of moist intrusions; its height dependence cannot be explained by the temperature difference between the emitting and absorbing layers, but by the decrease of water vapor extinction with altitude. This analytical work can help to narrow the search for low‐level cloud patterns sensitive to radiative‐convective feedbacks: the most organized patterns with largest cloud fractions occur in atmospheres below 10% relative humidity and feel the strongest low‐level cooling. This motivates further assessment of favorable conditions for radiative‐convective feedbacks and a robust quantification of corresponding shallow cloud dynamics in current and warmer climates.
Keywords: General Earth and Planetary Sciences

Mean structure of the supercritical turbulent spiral in Taylor–Couette flow - Wang, B.; Mellibovsky, F.; Ayats López, Roger; Deguchi, K.; Meseguer, A. (Philosophical Transactions of the Royal Society A)
The large-scale laminar/turbulent spiral patterns that appear in the linearly unstable regime of counter-rotating Taylor–Couette flow are investigated from a statistical perspective by means of direct numerical simulation. Unlike the vast majority of previous numerical studies, we analyse the flow in periodic parallelogram-annular domains, following a coordinate change that aligns one of the parallelogram sides with the spiral pattern. The domain size, shape and spatial resolution have been varied and the results compared with those in a sufficiently large computational orthogonal domain with natural axial and azimuthal periodicity. We find that a minimal parallelogram of the right tilt significantly reduces the computational cost without notably compromising the statistical properties of the supercritical turbulent spiral. Its mean structure, obtained from extremely long time integrations in a co-rotating reference frame using the method of slices, bears remarkable similarity with the turbulent stripes observed in plane Couette flow, the centrifugal instability playing only a secondary role.
Keywords: General Physics and Astronomy; General Engineering; General Mathematics

Low-pT quarkonium polarization measurements: Challenges and opportunities - Faccioli, Pietro; Krätschmer, Ilse; Lourenço, Carlos (Physics Letters B)
Several fixed-target experiments reported J/ψ and ϒ polarizations, as functions of Feynman x (xF) and transverse momentum (PT), in three different frames, using different combinations of beam particles, target nuclei, and collision energies. Despite the diverse and heterogeneous picture formed by these measurements, a detailed look allows us to discern qualitative physical patterns that inspire a simple empirical model. This data-driven scenario offers a good quantitative description of the J/ψ and ϒ(1S) polarizations measured in proton- and pion-nucleus collisions, in the xF 0.5 domain: more than 80 data points (not statistically independent) are well reproduced with only one free parameter. This study sets the context for future low-PT quarkonium polarization measurements in proton- and pion-nucleus collisions, such as those to be made by the AMBER experiment, and shows that such measurements provide significant constraints on the poorly-known parton distribution functions of the pion.
Keywords: Nuclear and High Energy Physics

Local laws for multiplication of random matrices - Ding, Xiucai; Ji, Hong Chang (The Annals of Applied Probability)
Consider the random matrix model A1/2UBU∗A1/2, where A and B are two N × N deterministic matrices and U is either an N × N Haar unitary or orthogonal random matrix. It is well known that on the macroscopic scale (Invent. Math. 104 (1991) 201–220), the limiting empirical spectral distribution (ESD) of the above model is given by the free multiplicative convolution of the limiting ESDs of A and B, denoted as μα μβ, where μα and μβ are the limiting ESDs of A and B, respectively. In this paper, we study the asymptotic microscopic behavior of the edge eigenvalues and eigenvectors statistics. We prove that both the density of μA μB, where μA and μB are the ESDs of A and B, respectively and the associated subordination functions have a regular behavior near the edges. Moreover, we establish the local laws near the edges on the optimal scale. In particular, we prove that the entries of the resolvent are close to some functionals depending only on the eigenvalues of A, B and the subordination functions with optimal convergence rates. Our proofs and calculations are based on the techniques developed for the additive model A+UBU∗ in (J. Funct. Anal. 271 (2016) 672–719; Comm. Math. Phys. 349 (2017) 947–990; Adv. Math. 319 (2017) 251–291; J. Funct. Anal. 279 (2020) 108639), and our results can be regarded as the counterparts of (J. Funct. Anal. 279 (2020) 108639) for the multiplicative model.
Keywords: Statistics; Probability and Uncertainty; Statistics and Probability

Fully extended r-spin TQFTs - Carqueville, Nils; Szegedy, Lorant (Quantum Topology)
We prove the r-spin cobordism hypothesis in the setting of (weak) 2-categories for every positive integer r: the 2-groupoid of 2-dimensional fully extended r-spin TQFTs with given target is equivalent to the homotopy fixed points of an induced Spin 2r -action. In particular, such TQFTs are classified by fully dualisable objects together with a trivialisation of the rth power of their Serre automorphisms. For r=1, we recover the oriented case (on which our proof builds), while ordinary spin structures correspond to r=2. To construct examples, we explicitly describe Spin 2r​-homotopy fixed points in the equivariant completion of any symmetric monoidal 2-category. We also show that every object in a 2-category of Landau–Ginzburg models gives rise to fully extended spin TQFTs and that half of these do not factor through the oriented bordism 2-category.
Keywords: Geometry and Topology; Mathematical Physics

Zero-error communication over adversarial MACs - Zhang, Yihan (IEEE Transactions on Information Theory)
We consider zero-error communication over a two-transmitter deterministic adversarial multiple access channel (MAC) governed by an adversary who has access to the transmissions of both senders (hence called omniscient ) and aims to maliciously corrupt the communication. None of the encoders, jammer and decoder is allowed to randomize using private or public randomness. This enforces a combinatorial nature of the problem. Our model covers a large family of channels studied in the literature, including all deterministic discrete memoryless noisy or noiseless MACs. In this work, given an arbitrary two-transmitter deterministic omniscient adversarial MAC, we characterize when the capacity region: 1) has nonempty interior (in particular, is two-dimensional); 2) consists of two line segments (in particular, has empty interior); 3) consists of one line segment (in particular, is one-dimensional); 4) or only contains (0,0) (in particular, is zero-dimensional). This extends a recent result by Wang et al. (201 9) from the point-to-point setting to the multiple access setting. Indeed, our converse arguments build upon their generalized Plotkin bound and involve delicate case analysis. One of the technical challenges is to take care of both “joint confusability” and “marginal confusability”. In particular, the treatment of marginal confusability does not follow from the point-to-point results by Wang et al. Our achievability results follow from random coding with expurgation.
Keywords: Computer Science Applications; Information Systems

Convergence of the scalar- and vector-valued Allen–Cahn equation to mean curvature flow with 90°-contact angle in higher dimensions, part I: Convergence result - Moser, Maximilian (Asymptotic Analysis)
We consider the sharp interface limit for the scalar-valued and vector-valued Allen–Cahn equation with homogeneous Neumann boundary condition in a bounded smooth domain Ω of arbitrary dimension N ⩾ 2 in the situation when a two-phase diffuse interface has developed and intersects the boundary ∂ Ω. The limit problem is mean curvature flow with 90°-contact angle and we show convergence in strong norms for well-prepared initial data as long as a smooth solution to the limit problem exists. To this end we assume that the limit problem has a smooth solution on [ 0 , T ] for some time T > 0. Based on the latter we construct suitable curvilinear coordinates and set up an asymptotic expansion for the scalar-valued and the vector-valued Allen–Cahn equation. In order to estimate the difference of the exact and approximate solutions with a Gronwall-type argument, a spectral estimate for the linearized Allen–Cahn operator in both cases is required. The latter will be shown in a separate paper, cf. (Moser (2021)).
Keywords: General Mathematics

Interplay of Cell‐autonomous Gene Function and Tissue‐wide Mechanisms Regulating Radial Glial Progenitor Lineage Progression - Villalba Requena, Ana; Amberg, Nicole; Hippenmeyer, Simon (Neocortical Neurogenesis in Development and Evolution)
The cerebral cortex is comprised of a vast cell-type diversity sequentially generated by cortical progenitor cells. Faithful progenitor lineage progression requires the tight orchestration of distinct molecular and cellular mechanisms regulating proper progenitor proliferation behavior and differentiation. Correct execution of developmental programs involves a complex interplay of cell intrinsic and tissue-wide mechanisms. Many studies over the past decades have been able to determine a plethora of genes critically involved in cortical development. However, only a few made use of genetic paradigms with sparse and global gene deletion to probe cell-autonomous vs. tissue-wide contribution. In this chapter, we will elaborate on the importance of dissecting the cell-autonomous and tissue-wide mechanisms to gain a precise understanding of gene function during radial glial progenitor lineage progression.

Analog stabilization of an electro-optic I/Q modulator with an auxiliary modulation tone - Wald, Sebastian; Diorico, Fritz R; Hosten, Onur (Applied Optics)
Proper operation of electro-optic I/Q modulators relies on precise adjustment and control of the relative phase biases between the modulator’s internal interferometer arms. We present an all-analog phase bias locking scheme where error signals are obtained from the beat between the optical carrier and optical tones generated by an auxiliary 2 MHz 𝑅𝐹 tone to lock the phases of all three involved interferometers for operation up to 10 GHz. With the developed method, we demonstrate an I/Q modulator in carrier-suppressed single-sideband mode, where the suppressed carrier and sideband are locked at optical power levels <−27dB relative to the transmitted sideband. We describe a simple analytical model for calculating the error signals and detail the implementation of the electronic circuitry for the implementation of the method.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Research data for the publication "Dense 4D nanoscale reconstruction of living brain tissue" - Danzl, Johann G
3D-reconstruction of living brain tissue down to individual synapse level would create opportunities for decoding the dynamics and structure-function relationships of the brain’s complex and dense information processing network. However, it has been hindered by insufficient 3D-resolution, inadequate signal-to-noise-ratio, and prohibitive light burden in optical imaging, whereas electron microscopy is inherently static. Here we solved these challenges by developing an integrated optical/machine learning technology, LIONESS (Live Information-Optimized Nanoscopy Enabling Saturated Segmentation). It leverages optical modifications to stimulated emission depletion (STED) microscopy in comprehensively, extracellularly labelled tissue and prior information on sample structure via machine learning to simultaneously achieve isotropic super-resolution, high signal-to-noise-ratio, and compatibility with living tissue. This allows dense deep-learning-based instance segmentation and 3D-reconstruction at synapse level incorporating molecular, activity, and morphodynamic information. LIONESS opens up avenues for studying the dynamic functional (nano-)architecture of living brain tissue.

Dense 4D nanoscale reconstruction of living brain tissue - Velicky, Philipp; Miguel Villalba, Eder; Michalska, Julia M; Lyudchik, Julia; Wei, Donglai; Lin, Zudi; Watson, Jake; Troidl, Jakob; Beyer, Johanna; Ben Simon, Yoav; Sommer, Christoph M; Jahr, Wiebke; et al. (Nature Methods)
Three-dimensional (3D) reconstruction of living brain tissue down to an individual synapse level would create opportunities for decoding the dynamics and structure–function relationships of the brain’s complex and dense information processing network; however, this has been hindered by insufficient 3D resolution, inadequate signal-to-noise ratio and prohibitive light burden in optical imaging, whereas electron microscopy is inherently static. Here we solved these challenges by developing an integrated optical/machine-learning technology, LIONESS (live information-optimized nanoscopy enabling saturated segmentation). This leverages optical modifications to stimulated emission depletion microscopy in comprehensively, extracellularly labeled tissue and previous information on sample structure via machine learning to simultaneously achieve isotropic super-resolution, high signal-to-noise ratio and compatibility with living tissue. This allows dense deep-learning-based instance segmentation and 3D reconstruction at a synapse level, incorporating molecular, activity and morphodynamic information. LIONESS opens up avenues for studying the dynamic functional (nano-)architecture of living brain tissue.

Bias in pruned vision models: In-depth analysis and countermeasures - Iofinova, Eugenia B; Peste, Elena-Alexandra; Alistarh, Dan-Adrian (2023 IEEE/CVF Conference on Computer Vision and Pattern Recognition)
Pruning—that is, setting a significant subset of the parameters of a neural network to zero—is one of the most popular methods of model compression. Yet, several recent works have raised the issue that pruning may induce or exacerbate bias in the output of the compressed model. Despite existing evidence for this phenomenon, the relationship between neural network pruning and induced bias is not well-understood. In this work, we systematically investigate and characterize this phenomenon in Convolutional Neural Networks for computer vision. First, we show that it is in fact possible to obtain highly-sparse models, e.g. with less than 10% remaining weights, which do not decrease in accuracy nor substantially increase in bias when compared to dense models. At the same time, we also find that, at higher sparsities, pruned models exhibit higher uncertainty in their outputs, as well as increased correlations, which we directly link to increased bias. We propose easy-to-use criteria which, based only on the uncompressed model, establish whether bias will increase with pruning, and identify the samples most susceptible to biased predictions post-compression. Our code can be found at https://github.com/IST-DASLab/pruned-vision-model-bias.

LIONESS enables 4D nanoscale reconstruction of living brain tissue - Danzl, Johann G; Velicky, Philipp (Nature Methods)
We developed LIONESS, a technology that leverages improvements to optical super-resolution microscopy and prior information on sample structure via machine learning to overcome the limitations (in 3D-resolution, signal-to-noise ratio and light exposure) of optical microscopy of living biological specimens. LIONESS enables dense reconstruction of living brain tissue and morphodynamics visualization at the nanoscale.
Keywords: Cell Biology; Molecular Biology; Biochemistry; Biotechnology

Real-time monitoring of an endogenous Fgf8a gradient attests to its role as a morphogen during zebrafish gastrulation - Harish, Rohit K; Gupta, Mansi; Zöller, Daniela; Hartmann, Hella; Gheisari, Ali; Machate, Anja; Hans, Stefan; Brand, Michael (Development)
Morphogen gradients impart positional information to cells in a homogenous tissue field. Fgf8a, a highly conserved growth factor, has been proposed to act as a morphogen during zebrafish gastrulation. However, technical limitations have so far prevented direct visualization of the endogenous Fgf8a gradient and confirmation of its morphogenic activity. Here, we monitor Fgf8a propagation in the developing neural plate using a CRISPR/Cas9-mediated EGFP knock-in at the endogenous fgf8a locus. By combining sensitive imaging with single-molecule fluorescence correlation spectroscopy, we demonstrate that Fgf8a, which is produced at the embryonic margin, propagates by diffusion through the extracellular space and forms a graded distribution towards the animal pole. Overlaying the Fgf8a gradient curve with expression profiles of its downstream targets determines the precise input-output relationship of Fgf8a-mediated patterning. Manipulation of the extracellular Fgf8a levels alters the signaling outcome, thus establishing Fgf8a as a bona fide morphogen during zebrafish gastrulation. Furthermore, by hindering Fgf8a diffusion, we demonstrate that extracellular diffusion of the protein from the source is crucial for it to achieve its morphogenic potential.
Keywords: Developmental Biology; Molecular Biology

Phytaspase Is capable of detaching the endoplasmic reticulum retrieval signal from tobacco calreticulin-3 - Teplova, Anastasiia; Pigidanov, Artemii A.; Serebryakova, Marina V.; Golyshev, Sergei A.; Galiullina, Raisa A.; Chichkova, Nina V.; Vartapetian, Andrey B. (International Journal of Molecular Sciences)
Soluble chaperones residing in the endoplasmic reticulum (ER) play vitally important roles in folding and quality control of newly synthesized proteins that transiently pass through the ER en route to their final destinations. These soluble residents of the ER are themselves endowed with an ER retrieval signal that enables the cell to bring the escaped residents back from the Golgi. Here, by using purified proteins, we showed that Nicotiana tabacum phytaspase, a plant aspartate-specific protease, introduces two breaks at the C-terminus of the N. tabacum ER resident calreticulin-3. These cleavages resulted in removal of either a dipeptide or a hexapeptide from the C-terminus of calreticulin-3 encompassing part or all of the ER retrieval signal. Consistently, expression of the calreticulin-3 derivative mimicking the phytaspase cleavage product in Nicotiana benthamiana cells demonstrated loss of the ER accumulation of the protein. Notably, upon its escape from the ER, calreticulin-3 was further processed by an unknown protease(s) to generate the free N-terminal (N) domain of calreticulin-3, which was ultimately secreted into the apoplast. Our study thus identified a specific proteolytic enzyme capable of precise detachment of the ER retrieval signal from a plant ER resident protein, with implications for the further fate of the escaped resident.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Convergence rate to the Tracy–Widom laws for the largest eigenvalue of sample covariance matrices - Schnelli, Kevin; Xu, Yuanyuan (The Annals of Applied Probability)
We establish a quantitative version of the Tracy–Widom law for the largest eigenvalue of high-dimensional sample covariance matrices. To be precise, we show that the fluctuations of the largest eigenvalue of a sample covariance matrix X∗X converge to its Tracy–Widom limit at a rate nearly N−1/3, where X is an M×N random matrix whose entries are independent real or complex random variables, assuming that both M and N tend to infinity at a constant rate. This result improves the previous estimate N−2/9 obtained by Wang (2019). Our proof relies on a Green function comparison method (Adv. Math. 229 (2012) 1435–1515) using iterative cumulant expansions, the local laws for the Green function and asymptotic properties of the correlation kernel of the white Wishart ensemble.
Keywords: Statistics; Probability and Uncertainty; Statistics and Probability

The cloud dynamics of convective storm systems - Muller, Caroline J; Abramian, Sophie (Physics Today)
Through a combination of idealized simulations and real-world data, researchers are uncovering how internal feedbacks and large-scale motions influence cloud dynamics.
Keywords: General Physics and Astronomy

Improvement of thermoelectric performance of flexible compound Ag2S0.55Se0.45 by means of partial V-substitution for Ag - Sato, Kosuke; Singh, Saurabh; Yamazaki, Itsuki; Hirata, Keisuke; Ang, Artoni Kevin R.; Matsunami, Masaharu; Takeuchi, Tsunehiro (AIP Advances)
The effects of the partial V-substitution for Ag on the thermoelectric (TE) properties are investigated for a flexible semiconducting compound Ag2S0.55Se0.45. Density functional theory calculations predict that such a partial V-substitution constructively modifies the electronic structure near the bottom of the conduction band to improve the TE performance. The synthesized Ag1.97V0.03S0.55Se0.45 is found to possess a TE dimensionless figure-of-merit (ZT) of 0.71 at 350 K with maintaining its flexible nature. This ZT value is relatively high in comparison with those reported for flexible TE materials below 360 K. The increase in the ZT value is caused by the enhanced absolute value of the Seebeck coefficient with less significant variation in electrical resistivity. The high ZT value with the flexible nature naturally allows us to employ the Ag1.97V0.03S0.55Se0.45 as a component of flexible TE generators.
Keywords: General Physics and Astronomy

Divergence of separated nets with respect to displacement equivalence - Dymond, Michael; Kaluza, Vojtech (Geometriae Dedicata)
We introduce a hierachy of equivalence relations on the set of separated nets of a given Euclidean space, indexed by concave increasing functions ϕ:(0,∞)→(0,∞). Two separated nets are called ϕ-displacement equivalent if, roughly speaking, there is a bijection between them which, for large radii R, displaces points of norm at most R by something of order at most ϕ(R). We show that the spectrum of ϕ-displacement equivalence spans from the established notion of bounded displacement equivalence, which corresponds to bounded ϕ, to the indiscrete equivalence relation, coresponding to ϕ(R)∈Ω(R), in which all separated nets are equivalent. In between the two ends of this spectrum, the notions of ϕ-displacement equivalence are shown to be pairwise distinct with respect to the asymptotic classes of ϕ(R) for R→∞. We further undertake a comparison of our notion of ϕ-displacement equivalence with previously studied relations on separated nets. Particular attention is given to the interaction of the notions of ϕ-displacement equivalence with that of bilipschitz equivalence.

Deterministic clustering in high dimensional spaces: Sketches and approximation - Cohen-Addad, Vincent; Saulpic, David; Schwiegelshohn, Chris (2023 IEEE 64th Annual Symposium on Foundations of Computer Science)
In all state-of-the-art sketching and coreset techniques for clustering, as well as in the best known fixed-parameter tractable approximation algorithms, randomness plays a key role. For the classic k-median and k-means problems, there are no known deterministic dimensionality reduction procedure or coreset construction that avoid an exponential dependency on the input dimension d, the precision parameter $ε^{-1}$ or k. Furthermore, there is no coreset construction that succeeds with probability $1-1/n$ and whose size does not depend on the number of input points, n. This has led researchers in the area to ask what is the power of randomness for clustering sketches [Feldman WIREs Data Mining Knowl. Discov’20].Similarly, the best approximation ratio achievable deterministically without a complexity exponential in the dimension are $1+\sqrt{2}$ for k-median [Cohen-Addad, Esfandiari, Mirrokni, Narayanan, STOC’22] and 6.12903 for k-means [Grandoni, Ostrovsky, Rabani, Schulman, Venkat, Inf. Process. Lett.’22]. Those are the best results, even when allowing a complexity FPT in the number of clusters k: this stands in sharp contrast with the $(1+ε)$-approximation achievable in that case, when allowing randomization.In this paper, we provide deterministic sketches constructions for clustering, whose size bounds are close to the best-known randomized ones. We show how to compute a dimension reduction onto $ε^{-O(1)} \log k$ dimensions in time $k^{O\left(ε^{-O(1)}+\log \log k\right)}$ poly $(n d)$, and how to build a coreset of size $O\left(k^{2} \log ^{3} k ε^{-O(1)}\right)$ in time $2^{ε^{O(1)} k \log ^{3} k}+k^{O\left(ε^{-O(1)}+\log \log k\right)}$ poly $(n d)$. In the case where k is small, this answers an open question of [Feldman WIDM’20] and [Munteanu and Schwiegelshohn, Künstliche Intell. ’18] on whether it is possible to efficiently compute coresets deterministically.We also construct a deterministic algorithm for computing $(1+$ $ε)$-approximation to k-median and k-means in high dimensional Euclidean spaces in time $2^{k^{2} \log ^{3} k / ε^{O(1)}}$ poly $(n d)$, close to the best randomized complexity of $2^{(k / ε)^{O(1)}}$ nd (see [Kumar, Sabharwal, Sen, JACM 10] and [Bhattacharya, Jaiswal, Kumar, TCS’18]).Furthermore, our new insights on sketches also yield a randomized coreset construction that uses uniform sampling, that immediately improves over the recent results of [Braverman et al. FOCS ’22] by a factor k.

Exposure of volunteers to microgravity by dry immersion bed over 21 days results in gene expression changes and adaptation of T cells - Gallardo-Dodd, Carlos J.; Oertlin, Christian; Record, Julien; Galvani, Rômulo G.; Sommerauer, Christian; Kuznetsov, Nikolai V.; Doukoumopoulos, Evangelos; Ali, Liaqat; Oliveira, Mariana M. S.; Seitz, Christina; Percipalle, Mathias; Nikić, Tijana; et al. (Science Advances)
The next steps of deep space exploration are manned missions to Moon and Mars. For safe space missions for crew members, it is important to understand the impact of space flight on the immune system. We studied the effects of 21 days dry immersion (DI) exposure on the transcriptomes of T cells isolated from blood samples of eight healthy volunteers. Samples were collected 7 days before DI, at day 7, 14, and 21 during DI, and 7 days after DI. RNA sequencing of CD3+T cells revealed transcriptional alterations across all time points, with most changes occurring 14 days after DI exposure. At day 21, T cells showed evidence of adaptation with a transcriptional profile resembling that of 7 days before DI. At 7 days after DI, T cells again changed their transcriptional profile. These data suggest that T cells adapt by rewiring their transcriptomes in response to simulated weightlessness and that remodeling cues persist when reexposed to normal gravity.
Keywords: Multidisciplinary

Branched actin cortices reconstituted in vesicles sense membrane curvature - Baldauf, Lucia; Frey, Felix F; Arribas Perez, Marcos; Idema, Timon; Koenderink, Gijsje H. (Biophysical Journal)
The actin cortex is a complex cytoskeletal machinery that drives and responds to changes in cell shape. It must generate or adapt to plasma membrane curvature to facilitate diverse functions such as cell division, migration, and phagocytosis. Due to the complex molecular makeup of the actin cortex, it remains unclear whether actin networks are inherently able to sense and generate membrane curvature, or whether they rely on their diverse binding partners to accomplish this. Here, we show that curvature sensing is an inherent capability of branched actin networks nucleated by Arp2/3 and VCA. We develop a robust method to encapsulate actin inside giant unilamellar vesicles (GUVs) and assemble an actin cortex at the inner surface of the GUV membrane. We show that actin forms a uniform and thin cortical layer when present at high concentration and distinct patches associated with negative membrane curvature at low concentration. Serendipitously, we find that the GUV production method also produces dumbbell-shaped GUVs, which we explain using mathematical modeling in terms of membrane hemifusion of nested GUVs. We find that branched actin networks preferentially assemble at the neck of the dumbbells, which possess a micrometer-range convex curvature comparable with the curvature of the actin patches found in spherical GUVs. Minimal branched actin networks can thus sense membrane curvature, which may help mammalian cells to robustly recruit actin to curved membranes to facilitate diverse cellular functions such as cytokinesis and migration.
Keywords: Biophysics

Astroglial connexin 43 regulates synaptic vesicle release at hippocampal synapses - Cheung, Giselle T; Chever, Oana; Rollenhagen, Astrid; Quenech’du, Nicole; Ezan, Pascal; Lübke, Joachim H. R.; Rouach, Nathalie (Cells)
Connexin 43, an astroglial gap junction protein, is enriched in perisynaptic astroglial processes and plays major roles in synaptic transmission. We have previously found that astroglial Cx43 controls synaptic glutamate levels and allows for activity-dependent glutamine release to sustain physiological synaptic transmissions and cognitiogns. However, whether Cx43 is important for the release of synaptic vesicles, which is a critical component of synaptic efficacy, remains unanswered. Here, using transgenic mice with a glial conditional knockout of Cx43 (Cx43−/−), we investigate whether and how astrocytes regulate the release of synaptic vesicles from hippocampal synapses. We report that CA1 pyramidal neurons and their synapses develop normally in the absence of astroglial Cx43. However, a significant impairment in synaptic vesicle distribution and release dynamics were observed. In particular, the FM1-43 assays performed using two-photon live imaging and combined with multi-electrode array stimulation in acute hippocampal slices, revealed a slower rate of synaptic vesicle release in Cx43−/− mice. Furthermore, paired-pulse recordings showed that synaptic vesicle release probability was also reduced and is dependent on glutamine supply via Cx43 hemichannel (HC). Taken together, we have uncovered a role for Cx43 in regulating presynaptic functions by controlling the rate and probability of synaptic vesicle release. Our findings further highlight the significance of astroglial Cx43 in synaptic transmission and efficacy.
Keywords: General Medicine

Role of natural transformation in the evolution of small cryptic plasmids in Synechocystis sp. PCC 6803 - Nies, Fabian; Wein, Tanita; Hanke, Dustin M.; Springstein, Benjamin L; Alcorta, Jaime; Taubenheim, Claudia; Dagan, Tal (Environmental Microbiology Reports)
Small cryptic plasmids have no clear effect on the host fitness and their functional repertoire remains obscure. The naturally competent cyanobacterium Synechocystis sp. PCC 6803 harbours several small cryptic plasmids; whether their evolution with this species is supported by horizontal transfer remains understudied. Here, we show that the small cryptic plasmid DNA is transferred in the population exclusively by natural transformation, where the transfer frequency of plasmid‐encoded genes is similar to that of chromosome‐encoded genes. Establishing a system to follow gene transfer, we compared the transfer frequency of genes encoded in cryptic plasmids pCA2.4 (2378 bp) and pCB2.4 (2345 bp) within and between populations of two Synechocystis sp. PCC 6803 labtypes (termed Kiel and Sevilla). Our results reveal that plasmid gene transfer frequency depends on the recipient labtype. Furthermore, gene transfer via whole plasmid uptake in the Sevilla labtype ranged among the lowest detected transfer rates in our experiments. Our study indicates that horizontal DNA transfer via natural transformation is frequent in the evolution of small cryptic plasmids that reside in naturally competent organisms. Furthermore, we suggest that the contribution of natural transformation to cryptic plasmid persistence in Synechocystis is limited.
Keywords: Agricultural and Biological Sciences (miscellaneous); Ecology; Evolution; Behavior and Systematics

Spiked multiplicative random matrices and principal components - Ding, Xiucai; Ji, Hong Chang (Stochastic Processes and their Applications)
In this paper, we study the eigenvalues and eigenvectors of the spiked invariant multiplicative models when the randomness is from Haar matrices. We establish the limits of the outlier eigenvalues λˆi and the generalized components (⟨v,uˆi⟩ for any deterministic vector v) of the outlier eigenvectors uˆi with optimal convergence rates. Moreover, we prove that the non-outlier eigenvalues stick with those of the unspiked matrices and the non-outlier eigenvectors are delocalized. The results also hold near the so-called BBP transition and for degenerate spikes. On one hand, our results can be regarded as a refinement of the counterparts of [12] under additional regularity conditions. On the other hand, they can be viewed as an analog of [34] by replacing the random matrix with i.i.d. entries with Haar random matrix.
Keywords: Applied Mathematics; Modeling and Simulation; Statistics and Probability

The decaying near‐surface boundary layer of a retreating alpine glacier - Shaw, Thomas E.; Buri, Pascal; McCarthy, Michael; Miles, Evan S.; Ayala, Álvaro; Pellicciotti, Francesca (Geophysical Research Letters)
The presence of a developed boundary layer decouples a glacier's response from ambient conditions, suggesting that sensitivity to climate change is increased by glacier retreat. To test this hypothesis, we explore six years of distributed meteorological data on a small Swiss glacier in the period 2001–2022. Large glacier fragmentation has occurred since 2001 (−35% area change up to 2022) coinciding with notable frontal retreat, an observed switch from down‐glacier katabatic to up‐glacier valley winds and an increased sensitivity (ratio) of on‐glacier to off‐glacier temperature. As the glacier ceases to develop density‐driven katabatic winds, sensible heat fluxes on the glacier are increasingly determined by the conditions occurring outside the boundary layer of the glacier, sealing the glacier's demise as the climate continues to warm and experience an increased frequency of extreme summers.
Keywords: General Earth and Planetary Sciences; Geophysics

Spatial organization and function of RNA molecules within phase-separated condensates in zebrafish are controlled by Dnd1 - Westerich, Kim Joana; Tarbashevich, Katsiaryna; Schick, Jan; Gupta, Antra; Zhu, Mingzhao; Hull, Kenneth; Romo, Daniel; Zeuschner, Dagmar; Goudarzi, Mohammad; Gross-Thebing, Theresa; Raz, Erez (Developmental Cell)
Germ granules, condensates of phase-separated RNA and protein, are organelles that are essential for germline development in different organisms. The patterning of the granules and their relevance for germ cell fate are not fully understood. Combining three-dimensional in vivo structural and functional analyses, we study the dynamic spatial organization of molecules within zebrafish germ granules. We find that the localization of RNA molecules to the periphery of the granules, where ribosomes are localized, depends on translational activity at this location. In addition, we find that the vertebrate-specific Dead end (Dnd1) protein is essential for nanos3 RNA localization at the condensates’ periphery. Accordingly, in the absence of Dnd1, or when translation is inhibited, nanos3 RNA translocates into the granule interior, away from the ribosomes, a process that is correlated with the loss of germ cell fate. These findings highlight the relevance of sub-granule compartmentalization for post-transcriptional control and its importance for preserving germ cell totipotency.
Keywords: Developmental Biology; Cell Biology; General Biochemistry; Genetics and Molecular Biology; Molecular Biology

Automated verification and control of infinite state stochastic systems - Zikelic, Dorde
Stochastic systems provide a formal framework for modelling and quantifying uncertainty in systems and have been widely adopted in many application domains. Formal verification and control of finite state stochastic systems, a subfield of formal methods also known as probabilistic model checking, is well studied. In contrast, formal verification and control of infinite state stochastic systems have received comparatively less attention. However, infinite state stochastic systems commonly arise in practice. For instance, probabilistic models that contain continuous probability distributions such as normal or uniform, or stochastic dynamical systems which are a classical model for control under uncertainty, both give rise to infinite state systems. The goal of this thesis is to contribute to laying theoretical and algorithmic foundations of fully automated formal verification and control of infinite state stochastic systems, with a particular focus on systems that may be executed over a long or infinite time. We consider formal verification of infinite state stochastic systems in the setting of static analysis of probabilistic programs and formal control in the setting of controller synthesis in stochastic dynamical systems. For both problems, we present some of the first fully automated methods for probabilistic (a.k.a. quantitative) reachability and safety analysis applicable to infinite time horizon systems. We also advance the state of the art of probability 1 (a.k.a. qualitative) reachability analysis for both problems. Finally, for formal controller synthesis in stochastic dynamical systems, we present a novel framework for learning neural network control policies in stochastic dynamical systems with formal guarantees on correctness with respect to quantitative reachability, safety or reach-avoid specifications.

Clathrin coats partially preassemble and subsequently bend during endocytosis - Mund, Markus; Tschanz, Aline; Wu, Yu-Le; Frey, Felix F; Mehl, Johanna L.; Kaksonen, Marko; Avinoam, Ori; Schwarz, Ulrich S.; Ries, Jonas (Journal of Cell Biology)
Eukaryotic cells use clathrin-mediated endocytosis to take up a large range of extracellular cargo. During endocytosis, a clathrin coat forms on the plasma membrane, but it remains controversial when and how it is remodeled into a spherical vesicle. Here, we use 3D superresolution microscopy to determine the precise geometry of the clathrin coat at large numbers of endocytic sites. Through pseudo-temporal sorting, we determine the average trajectory of clathrin remodeling during endocytosis. We find that clathrin coats assemble first on flat membranes to 50% of the coat area before they become rapidly and continuously bent, and this mechanism is confirmed in three cell lines. We introduce the cooperative curvature model, which is based on positive feedback for curvature generation. It accurately describes the measured shapes and dynamics of the clathrin coat and could represent a general mechanism for clathrin coat remodeling on the plasma membrane.
Keywords: Cell Biology

First insight in element localisation in different body parts of the acanthocephalan Dentitruncus truttae using TEM and NanoSIMS - Filipović Marijić, Vlatka; Subirana, Maria Angels; Schaumlöffel, Dirk; Barišić, Josip; Gontier, Etienne; Krasnici, Nesrete; Mijošek, Tatjana; Hernández-Orts, Jesús S.; Scholz, Tomáš; Erk, Marijana (Science of The Total Environment)
Acanthocephalans, intestinal parasites of vertebrates, are characterised by orders of magnitude higher metal accumulation than free-living organisms, but the mechanism of such effective metal accumulation is still unknown. The aim of our study was to gain new insights into the high-resolution localization of elements in the bodies of acanthocephalans, thus taking an initial step towards elucidating metal uptake and accumulation in organisms under real environmental conditions. For the first time, nanoscale secondary ion mass spectrometry (NanoSIMS) was used for high-resolution mapping of 12 elements (C, Ca, Cu, Fe, N, Na, O, P, Pb, S, Se, and Tl) in three selected body parts (trunk spines, inner part of the proboscis receptacle and inner surface of the tegument) of Dentitruncus truttae, a parasite of brown trout (Salmo trutta) from the Krka River in Croatia. In addition, the same body parts were examined using transmission electron microscopy (TEM) and correlated with NanoSIMS images. Metal concentrations determined using HR ICP-MS confirmed higher accumulation in D. truttae than in the fish intestine. The chemical composition of the acanthocephalan body showed the highest density of C, Ca, N, Na, O, S, as important and constitutive elements in living cells in all studied structures, while Fe was predominant among trace elements. In general, higher element density was found in trunk spines and tegument, as body structures responsible for substance absorption in parasites. The results obtained with NanoSIMS and TEM-NanoSIMS correlative imaging represent pilot data for mapping of elements at nanoscale resolution in the ultrastructure of various body parts of acanthocephalans and generally provide a contribution for further application of this technique in all parasite species.
Keywords: Pollution; Waste Management and Disposal; Environmental Chemistry; Environmental Engineering

Integrating top‐down and bottom‐up approaches to understand the genetic architecture of speciation across a monkeyflower hybrid zone - Stankowski, Sean; Chase, Madeline A.; McIntosh, Hanna; Streisfeld, Matthew A. (Molecular Ecology)
Understanding the phenotypic and genetic architecture of reproductive isolation is a long‐standing goal of speciation research. In several systems, large‐effect loci contributing to barrier phenotypes have been characterized, but such causal connections are rarely known for more complex genetic architectures. In this study, we combine “top‐down” and “bottom‐up” approaches with demographic modelling toward an integrated understanding of speciation across a monkeyflower hybrid zone. Previous work suggests that pollinator visitation acts as a primary barrier to gene flow between two divergent red‐ and yellow‐flowered ecotypes of Mimulus aurantiacus . Several candidate isolating traits and anonymous single nucleotide polymorphism loci under divergent selection have been identified, but their genomic positions remain unknown. Here, we report findings from demographic analyses that indicate this hybrid zone formed by secondary contact, but that subsequent gene flow was restricted by widespread barrier loci across the genome. Using a novel, geographic cline‐based genome scan, we demonstrate that candidate barrier loci are broadly distributed across the genome, rather than mapping to one or a few “islands of speciation.” Quantitative trait locus (QTL) mapping reveals that most floral traits are highly polygenic, with little evidence that QTL colocalize, indicating that most traits are genetically independent. Finally, we find little evidence that QTL and candidate barrier loci overlap, suggesting that some loci contribute to other forms of reproductive isolation. Our findings highlight the challenges of understanding the genetic architecture of reproductive isolation and reveal that barriers to gene flow other than pollinator isolation may play an important role in this system.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

Modelling the dynamics of mammalian gut homeostasis - Corominas-Murtra, Bernat; Hannezo, Edouard B (Seminars in Cell & Developmental Biology)
Homeostatic balance in the intestinal epithelium relies on a fast cellular turnover, which is coordinated by an intricate interplay between biochemical signalling, mechanical forces and organ geometry. We review recent modelling approaches that have been developed to understand different facets of this remarkable homeostatic equilibrium. Existing models offer different, albeit complementary, perspectives on the problem. First, biomechanical models aim to explain the local and global mechanical stresses driving cell renewal as well as tissue shape maintenance. Second, compartmental models provide insights into the conditions necessary to keep a constant flow of cells with well-defined ratios of cell types, and how perturbations can lead to an unbalance of relative compartment sizes. A third family of models address, at the cellular level, the nature and regulation of stem fate choices that are necessary to fuel cellular turnover. We also review how these different approaches are starting to be integrated together across scales, to provide quantitative predictions and new conceptual frameworks to think about the dynamics of cell renewal in complex tissues.
Keywords: Cell Biology; Developmental Biology

On type II degenerations of hyperkähler manifolds - Huybrechts, D.; Mauri, Mirko (Mathematical Research Letters)
We give a simple argument to prove Nagai’s conjecture for type II degenerations of compact hyperkähler manifolds and cohomology classes of middle degree. Under an additional assumption, the techniques yield the conjecture in arbitrary degree. This would complete the proof of Nagai’s conjecture in general, as it was proved already for type I degenerations by Kollár, Laza, Saccà, and Voisin [10] and independently by Soldatenkov [18], while it is immediate for type III degenerations. Our arguments are close in spirit to a recent paper by Harder [8] proving similar results for the restrictive class of good degenerations.

External forces in the continuum limit of discrete systems with non-convex interaction potentials: Compactness for a Γ-development - Carioni, Marcello; Fischer, Julian L; Schlömerkemper, Anja (Journal of Convex Analysis)
This paper is concerned with equilibrium configurations of one-dimensional particle systems with non-convex nearest-neighbour and next-to-nearest-neighbour interactions and its passage to the continuum. The goal is to derive compactness results for a Γ-development of the energy with the novelty that external forces are allowed. In particular, the forces may depend on Lagrangian or Eulerian coordinates and thus may model dead as well as live loads. Our result is based on a new technique for deriving compactness results which are required for calculating the first-order Γ-limit in the presence of external forces: instead of comparing a configuration of n atoms to a global minimizer of the Γ-limit, we compare the configuration to a minimizer in some subclass of functions which in some sense are "close to" the configuration. The paper is complemented with the study of the minimizers of the Γ-limit.

The human factor: Results of a small-angle scattering data analysis round robin - Pauw, Brian R.; Smales, Glen J.; Anker, Andy S.; Annadurai, Venkatasamy; Balazs, Daniel; Bienert, Ralf; Bouwman, Wim G.; Breßler, Ingo; Breternitz, Joachim; Brok, Erik S.; Bryant, Gary; Clulow, Andrew J.; et al. (Journal of Applied Crystallography)
A round-robin study has been carried out to estimate the impact of the human element in small-angle scattering data analysis. Four corrected datasets were provided to participants ready for analysis. All datasets were measured on samples containing spherical scatterers, with two datasets in dilute dispersions and two from powders. Most of the 46 participants correctly identified the number of populations in the dilute dispersions, with half of the population mean entries within 1.5% and half of the population width entries within 40%. Due to the added complexity of the structure factor, far fewer people submitted answers on the powder datasets. For those that did, half of the entries for the means and widths were within 44 and 86%, respectively. This round-robin experiment highlights several causes for the discrepancies, for which solutions are proposed.

The effect of display capabilities on the gloss consistency between real and virtual objects - Chen, Bin; Jindal, Akshay; Piovarci, Michael; Wang, Chao; Seidel, Hans Peter; Didyk, Piotr; Myszkowski, Karol; Serrano, Ana; Mantiuk, Rafał K. (Proceedings of the SIGGRAPH Asia 2023 Conference)
A faithful reproduction of gloss is inherently difficult because of the limited dynamic range, peak luminance, and 3D capabilities of display devices. This work investigates how the display capabilities affect gloss appearance with respect to a real-world reference object. To this end, we employ an accurate imaging pipeline to achieve a perceptual gloss match between a virtual and real object presented side-by-side on an augmented-reality high-dynamic-range (HDR) stereoscopic display, which has not been previously attained to this extent. Based on this precise gloss reproduction, we conduct a series of gloss matching experiments to study how gloss perception degrades based on individual factors: object albedo, display luminance, dynamic range, stereopsis, and tone mapping. We support the study with a detailed analysis of individual factors, followed by an in-depth discussion on the observed perceptual effects. Our experiments demonstrate that stereoscopic presentation has a limited effect on the gloss matching task on our HDR display. However, both reduced luminance and dynamic range of the display reduce the perceived gloss. This means that the visual system cannot compensate for the changes in gloss appearance across luminance (lack of gloss constancy), and the tone mapping operator should be carefully selected when reproducing gloss on a low dynamic range (LDR) display.

On biased compression for distributed learning - Beznosikov, Aleksandr; Horvath, Samuel; Richtarik, Peter; Safaryan, Mher (Journal of Machine Learning Research)
In the last few years, various communication compression techniques have emerged as an indispensable tool helping to alleviate the communication bottleneck in distributed learning. However, despite the fact biased compressors often show superior performance in practice when compared to the much more studied and understood unbiased compressors, very little is known about them. In this work we study three classes of biased compression operators, two of which are new, and their performance when applied to (stochastic) gradient descent and distributed (stochastic) gradient descent. We show for the first time that biased compressors can lead to linear convergence rates both in the single node and distributed settings. We prove that distributed compressed SGD method, employed with error feedback mechanism, enjoys the ergodic rate O(δLexp[−μKδL]+(C+δD)Kμ), where δ≥1 is a compression parameter which grows when more compression is applied, L and μ are the smoothness and strong convexity constants, C captures stochastic gradient noise (C=0 if full gradients are computed on each node) and D captures the variance of the gradients at the optimum (D=0 for over-parameterized models). Further, via a theoretical study of several synthetic and empirical distributions of communicated gradients, we shed light on why and by how much biased compressors outperform their unbiased variants. Finally, we propose several new biased compressors with promising theoretical guarantees and practical performance.

Shortest dominating set reconfiguration under token sliding - Křišťan, Jan Matyáš; Svoboda, Jakub (24th International Symposium on Fundamentals of Computation Theory)
In this paper, we present novel algorithms that efficiently compute a shortest reconfiguration sequence between two given dominating sets in trees and interval graphs under the TOKEN SLIDING model. In this problem, a graph is provided along with its two dominating sets, which can be imagined as tokens placed on vertices. The objective is to find a shortest sequence of dominating sets that transforms one set into the other, with each set in the sequence resulting from sliding a single token in the previous set. While identifying any sequence has been well studied, our work presents the first polynomial algorithms for this optimization variant in the context of dominating sets.

Proof of availability and retrieval in a modular blockchain architecture - Cohen, Shir; Goren, Guy; Kokoris Kogias, Eleftherios; Sonnino, Alberto; Spiegelman, Alexander (27th International Conference on Financial Cryptography and Data Security)
This paper explores a modular design architecture aimed at helping blockchains (and other SMR implementation) to scale to a very large number of processes. This comes in contrast to existing monolithic architectures that interleave transaction dissemination, ordering, and execution in a single functionality. To achieve this we first split the monolith to multiple layers which can use existing distributed computing primitives. The exact specifications of the data dissemination part are formally defined by the Proof of Availability & Retrieval (PoA &R) abstraction. Solutions to the PoA &R problem contain two related sub-protocols: one that “pushes” information into the network and another that “pulls” this information. Regarding the latter, there is a dearth of research literature which is rectified in this paper. We present a family of pulling sub-protocols and rigorously analyze them. Extensive simulations support the theoretical claims of efficiency and robustness in case of a very large number of players. Finally, actual implementation and deployment on a small number of machines (roughly the size of several industrial systems) demonstrates the viability of the architecture’s paradigm.

Connecting theory and experiment in cell and tissue mechanics - Schwayer, Cornelia; Brückner, David (Journal of Cell Science)
Understanding complex living systems, which are fundamentally constrained by physical phenomena, requires combining experimental data with theoretical physical and mathematical models. To develop such models, collaborations between experimental cell biologists and theoreticians are increasingly important but these two groups often face challenges achieving mutual understanding. To help navigate these challenges, this Perspective discusses different modelling approaches, including bottom-up hypothesis-driven and top-down data-driven models, and highlights their strengths and applications. Using cell mechanics as an example, we explore the integration of specific physical models with experimental data from the molecular, cellular and tissue level up to multiscale input. We also emphasize the importance of constraining model complexity and outline strategies for crosstalk between experimental design and model development. Furthermore, we highlight how physical models can provide conceptual insights and produce unifying and generalizable frameworks for biological phenomena. Overall, this Perspective aims to promote fruitful collaborations that advance our understanding of complex biological systems.
Keywords: Cell Biology

Learning control policies for stochastic systems with reach-avoid guarantees - Zikelic, Dorde; Lechner, Mathias; Henzinger, Thomas A; Chatterjee, Krishnendu (Proceedings of the 37th AAAI Conference on Artificial Intelligence)
We study the problem of learning controllers for discrete-time non-linear stochastic dynamical systems with formal reach-avoid guarantees. This work presents the first method for providing formal reach-avoid guarantees, which combine and generalize stability and safety guarantees, with a tolerable probability threshold p in [0,1] over the infinite time horizon. Our method leverages advances in machine learning literature and it represents formal certificates as neural networks. In particular, we learn a certificate in the form of a reach-avoid supermartingale (RASM), a novel notion that we introduce in this work. Our RASMs provide reachability and avoidance guarantees by imposing constraints on what can be viewed as a stochastic extension of level sets of Lyapunov functions for deterministic systems. Our approach solves several important problems -- it can be used to learn a control policy from scratch, to verify a reach-avoid specification for a fixed control policy, or to fine-tune a pre-trained policy if it does not satisfy the reach-avoid specification. We validate our approach on 3 stochastic non-linear reinforcement learning tasks.
Keywords: General Medicine

On kinetic constraints that catalysis imposes on elementary processes - Sakref, Yann; Muñoz Basagoiti, Maitane; Zeravcic, Zorana; Rivoire, Olivier (The Journal of Physical Chemistry B)
Catalysis, the acceleration of product formation by a substance that is left unchanged, typically results from multiple elementary processes, including diffusion of the reactants toward the catalyst, chemical steps, and release of the products. While efforts to design catalysts are often focused on accelerating the chemical reaction on the catalyst, catalysis is a global property of the catalytic cycle that involves all processes. These are controlled by both intrinsic parameters such as the composition and shape of the catalyst and extrinsic parameters such as the concentration of the chemical species at play. We examine here the conditions that catalysis imposes on the different steps of a reaction cycle and the respective role of intrinsic and extrinsic parameters of the system on the emergence of catalysis by using an approach based on first-passage times. We illustrate this approach for various decompositions of a catalytic cycle into elementary steps, including non-Markovian decompositions, which are useful when the presence and nature of intermediate states are a priori unknown. Our examples cover different types of reactions and clarify the constraints on elementary steps and the impact of species concentrations on catalysis.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Nonadditivity in interactions between three membrane-wrapped colloidal spheres - Azadbakht, Ali; Meadowcroft, Billie; Majek, Juraj; Šarić, Anđela; Kraft, Daniela J. (Biophysical Journal)
Many cell functions require a concerted effort from multiple membrane proteins, for example, for signaling, cell division, and endocytosis. One contribution to their successful self-organization stems from the membrane deformations that these proteins induce. While the pairwise interaction potential of two membrane-deforming spheres has recently been measured, membrane-deformation-induced interactions have been predicted to be nonadditive, and hence their collective behavior cannot be deduced from this measurement. We here employ a colloidal model system consisting of adhesive spheres and giant unilamellar vesicles to test these predictions by measuring the interaction potential of the simplest case of three membrane-deforming, spherical particles. We quantify their interactions and arrangements and, for the first time, experimentally confirm and quantify the nonadditive nature of membrane-deformation-induced interactions. We furthermore conclude that there exist two favorable configurations on the membrane: (1) a linear and (2) a triangular arrangement of the three spheres. Using Monte Carlo simulations, we corroborate the experimentally observed energy minima and identify a lowering of the membrane deformation as the cause for the observed configurations. The high symmetry of the preferred arrangements for three particles suggests that arrangements of many membrane-deforming objects might follow simple rules.

Cover Picture: The rigid core and flexible surface of amyloid fibrils probed by Magic‐Angle‐Spinning NMR spectroscopy of aromatic residues - Becker, Lea Marie; Berbon, Mélanie; Vallet, Alicia; Grelard, Axelle; Morvan, Estelle; Bardiaux, Benjamin; Lichtenecker, Roman; Ernst, Matthias; Loquet, Antoine; Schanda, Paul (Angewandte Chemie International Edition)
Cover Page
Keywords: General Chemistry; Catalysis

On the rightmost eigenvalue of non-Hermitian random matrices - Cipolloni, Giorgio; Erdös, László; Schröder, Dominik J; Xu, Yuanyuan (The Annals of Probability)
We establish a precise three-term asymptotic expansion, with an optimal estimate of the error term, for the rightmost eigenvalue of an n×n random matrix with independent identically distributed complex entries as n tends to infinity. All terms in the expansion are universal.
Keywords: Statistics; Probability and Uncertainty; Statistics and Probability

Der starre Kern und die flexible Oberfläche von Amyloidfibrillen – Magic‐Angle‐Spinning NMR Spektroskopie von aromatischen Resten - Becker, Lea Marie; Berbon, Mélanie; Vallet, Alicia; Grelard, Axelle; Morvan, Estelle; Bardiaux, Benjamin; Lichtenecker, Roman; Ernst, Matthias; Loquet, Antoine; Schanda, Paul (Angewandte Chemie)
Aromatische Seitenketten sind wichtige Indikatoren für die Plastizität von Proteinen und bilden oft entscheidende Kontakte bei Protein‐Protein‐Wechselwirkungen. Wir untersuchten aromatische Reste in den beiden strukturell homologen cross‐β Amyloidfibrillen HET‐s und HELLF mit Hilfe eines spezifischen Ansatzes zur Isotopenmarkierung und Festkörper NMR mit Drehung am magischen Winkel. Das dynamische Verhalten der aromatischen Reste Phe und Tyr deutet darauf hin, dass der hydrophobe Amyloidkern starr ist und keine Anzeichen von “atmenden Bewegungen” auf einer Zeitskala von Hunderten von Millisekunden zeigt. Aromatische Reste, die exponiert an der Fibrillenoberfläche sitzen, haben zwar eine starre Ringachse, weisen aber Ringflips auf verschiedenen Zeitskalen von Nanosekunden bis Mikrosekunden auf. Unser Ansatz bietet einen direkten Einblick in die Bewegungen des hydrophoben Kerns und ermöglicht eine bessere Bewertung der Konformationsheterogenität, die aus einem NMR‐Strukturensemble einer solchen Cross‐β‐Amyloidstruktur hervorgeht.
Keywords: General Medicine

Mechanisms for the Self‐Organization of Tropical Deep Convection - Haerter, Jan O.; Muller, Caroline J (Clouds and Their Climatic Impacts)
Organization – or departure from a random pattern – in tropical deep convection is heavily studied due to its immediate relevance to climate sensitivity and extremes. Low-latitude convection has motivated numerical model idealizations, where the Coriolis force is removed and boundary conditions are simplified spatially and temporally. One of the most stunning aspects of such idealized simulated cloud organization is the spontaneous clumping of convection that can occur without any predetermining external perturbation, such as inhomogeneous surface boundary conditions or large-scale waves. Whereas individual convective rain cells measure only few kilometers in horizontal diameter, the clusters they form can often span hundreds or even thousands of kilometers. Hence, organization may emerge from the very small scales but can show effects at the synoptic scale. We refer to such emergent organization as convective self-organization. Convective self-organization thus features characteristics of emergence, such as non-trivial system-scale pattern formation or hysteresis. We summarize observational evidence for large-scale organization and briefly recap classical idealized modeling studies that yield convective self-aggregation – emergent organization under strongly idealized boundary conditions. We then focus on developing research, where temporal variation, such as the diurnal cycle, or two-way interactive surface properties yield distinct organizational modes. Convectively generated cold pools and mesoscale convective systems, both ubiquitous in nature, are thereby found to potentially play key roles in promoting – rather than suppressing – sustained system-scale organization.

Preparing Chaperone–Client Protein Complexes for Biophysical and Structural Studies - Sučec, I.; Schanda, Paul (Biophysics of Molecular Chaperones)
Understanding the mechanisms of chaperones at the atomic level generally requires producing chaperone–client complexes in vitro. This task comes with significant challenges, because one needs to find conditions in which the client protein is presented to the chaperone in a state that binds and at the same time avoid the pitfalls of protein aggregation that are often inherent to such states. The strategy differs significantly for different client proteins and chaperones, but there are common underlying principles. Here, we discuss these principles and deduce the strategies that can be successfully applied for different chaperone–client complexes. We review successful biochemical strategies applied to making the client protein “binding competent” and illustrate the different strategies with examples of recent biophysical and biochemical studies.

Probing Single Chaperone Substrates - Wruck, F.; Avellaneda Sarrió, Mario; Naqvi, M. M.; Koers, E. J.; Till, K.; Gross, L.; Moayed, F.; Roland, A.; Heling, L. W. H. J.; Mashaghi, A.; Tans, S. J. (Biophysics of Molecular Chaperones)
Regulating protein states is considered the core function of chaperones. However, despite their importance to all major cellular processes, the conformational changes that chaperones impart on polypeptide chains are difficult to study directly due to their heterogeneous, dynamic, and multi-step nature. Here, we review recent advances towards this aim using single-molecule manipulation methods, which are rapidly revealing new mechanisms of conformational control and helping to define a different perspective on the chaperone function.

Ubiquity of bound states for the strongly coupled polaron - Mitrouskas, David Johannes; Seiringer, Robert (Pure and Applied Analysis)
Abstract We study the spectrum of the Fröhlich Hamiltonian for the polaron at fixed total momentum. We prove the existence of excited eigenvalues between the ground state energy and the essential spectrum at strong coupling. In fact, our main result shows that the number of excited energy bands diverges in the strong coupling limit. To prove this we derive upper bounds for the min-max values of the corresponding fiber Hamiltonians and compare them with the bottom of the essential spectrum, a lower bound on which was recently obtained by Brooks and Seiringer (Comm. Math. Phys. 404:1 (2023), 287–337). The upper bounds are given in terms of the ground state energy band shifted by momentum-independent excitation energies determined by an effective Hamiltonian of Bogoliubov type.
Keywords: General Medicine

Entangling microwaves and telecom wavelength light - Sahu, Rishabh; Qiu, Liu; Hease, William J; Arnold, Georg M; Minoguchi, Yuri; Rabl, Peter; Fink, Johannes M (Frontiers in Optics + Laser Science 2023)
We entangled microwave and optical photons for the first time as verified by a measured two-mode vacuum squeezing of 0.7 dB. This electro-optic entanglement is the key resource needed to connect cryogenic quantum circuits.

Constructing Hamilton cycles and perfect matchings efficiently - Anastos, Michael (Proceedings of the 12th European Conference on Combinatorics, Graph Theory and Applications)
Starting with the empty graph on $[n]$, at each round, a set of $K=K(n)$ edges is presented chosen uniformly at random from the ones that have not been presented yet. We are then asked to choose at most one of the presented edges and add it to the current graph. Our goal is to construct a Hamiltonian graph with $(1+o(1))n$ edges within as few rounds as possible. We show that in this process, one can build a Hamiltonian graph of size $(1+o(1))n$ in $(1+o(1))(1+(\log n)/2K) n$ rounds w.h.p. The case $K=1$ implies that w.h.p. one can build a Hamiltonian graph by choosing $(1+o(1))n$ edges in an online fashion as they appear along the first $(0.5+o(1))n\log n$ rounds of the random graph process. This answers a question of Frieze, Krivelevich and Michaeli. Observe that the number of rounds is asymptotically optimal as the first $0.5n\log n$ edges do not span a Hamilton cycle w.h.p. The case $K=Θ(\log n)$ implies that the Hamiltonicity threshold of the corresponding Achlioptas process is at most $(1+o(1))(1+(\log n)/2K) n$. This matches the $(1-o(1))(1+(\log n)/2K) n$ lower bound due to Krivelevich, Lubetzky and Sudakov and resolves the problem of determining the Hamiltonicity threshold of the Achlioptas process with $K=Θ(\log n)$. We also show that in the above process one can construct a graph $G$ that spans a matching of size $\lfloor V(G)/2) \rfloor$ and $(0.5+o(1))n$ edges within $(1+o(1))(0.5+(\log n)/2K) n$ rounds w.h.p. Our proof relies on a robust Hamiltonicity property of the strong $4$-core of the binomial random graph which we use as a black-box. This property allows it to absorb paths covering vertices outside the strong $4$-core into a cycle.

Measuring spontaneous charging of single aerosol particles - Stöllner, Andrea; Lenton, Isaac C; Muller, Caroline J; Waitukaitis, Scott R (EGU General Assembly 2023)

Complex vaccination strategies prevent the emergence of vaccine resistance - Rella, Simon; Kulikova, Y; Minnegalieva, Aygul; Kondrashov, Fyodor (European Journal of Public Health)
Keywords: Public Health; Environmental and Occupational Health

Intensification mechanisms of tropical cyclones - Polesello, Andrea; Muller, Caroline J; Pasquero, Claudia; Meroni, Agostino N. (EGU General Assembly 2023)

PCBend: Light up your 3D shapes with foldable circuit boards - Freire, Marco; Bhargava, Manas; Schreck, Camille; Hugron, Pierre-Alexandre; Bickel, Bernd; Lefebvre, Sylvain (Transactions on Graphics)
We propose a computational design approach for covering a surface with individually addressable RGB LEDs, effectively forming a low-resolution surface screen. To achieve a low-cost and scalable approach, we propose creating designs from flat PCB panels bent in-place along the surface of a 3D printed core. Working with standard rigid PCBs enables the use of established PCB manufacturing services, allowing the fabrication of designs with several hundred LEDs. Our approach optimizes the PCB geometry for folding, and then jointly optimizes the LED packing, circuit and routing, solving a challenging layout problem under strict manufacturing requirements. Unlike paper, PCBs cannot bend beyond a certain point without breaking. Therefore, we introduce parametric cut patterns acting as hinges, designed to allow bending while remaining compact. To tackle the joint optimization of placement, circuit and routing, we propose a specialized algorithm that splits the global problem into one sub-problem per triangle, which is then individually solved. Our technique generates PCB blueprints in a completely automated way. After being fabricated by a PCB manufacturing service, the boards are bent and glued by the user onto the 3D printed support. We demonstrate our technique on a range of physical models and virtual examples, creating intricate surface light patterns from hundreds of LEDs.
Keywords: PCB design and layout; Mesh geometry models

Distinct functions of TIR1 and AFB1 receptors in auxin signalling. - Chen, Huihuang; Li, Lanxin; Zou, Minxia; Qi, Linlin; Friml, Jiří (Molecular Plant)
Auxin is the major plant hormone regulating growth and development (Friml, 2022). Forward genetic approaches in the model plant Arabidopsis thaliana have identified major components of auxin signalling and established the canonical mechanism mediating transcriptional and thus developmental reprogramming. In this textbook view, TRANSPORT INHIBITOR RESPONSE 1 (TIR1)/AUXIN-SIGNALING F-BOX (AFBs) are auxin receptors, which act as F-box subunits determining the substrate specificity of the Skp1-Cullin1-F box protein (SCF) type E3 ubiquitin ligase complex. Auxin acts as a “molecular glue” increasing the affinity between TIR1/AFBs and the Aux/IAA repressors. Subsequently, Aux/IAAs are ubiquitinated and degraded, thus releasing auxin transcription factors from their repression making them free to mediate transcription of auxin response genes (Yu et al., 2022). Nonetheless, accumulating evidence suggests existence of rapid, non-transcriptional responses downstream of TIR1/AFBs such as auxin-induced cytosolic calcium (Ca2+) transients, plasma membrane depolarization and apoplast alkalinisation, all converging on the process of root growth inhibition and root gravitropism (Li et al., 2022). Particularly, these rapid responses are mostly contributed by predominantly cytosolic AFB1, while the long-term growth responses are mediated by mainly nuclear TIR1 and AFB2-AFB5 (Li et al., 2021; Prigge et al., 2020; Serre et al., 2021). How AFB1 conducts auxin-triggered rapid responses and how it is different from TIR1 and AFB2-AFB5 remains elusive. Here, we compare the roles of TIR1 and AFB1 in transcriptional and rapid responses by modulating their subcellular localization in Arabidopsis and by testing their ability to mediate transcriptional responses when part of the minimal auxin circuit reconstituted in yeast.

douglastome/dynamic-engrams: Dynamic and selective engrams emerge with memory consolidation - Feitosa Tomé, Douglas
Code and data necessary to reproduce the simulations and data analyses reported in our manuscript: Tomé, D.F., Zhang, Y., Aida, T., Mosto, O., Lu, Y., Chen, M., Sadeh, S., Roy, D. S., Clopath, C. Dynamic and selective engrams emerge with memory consolidation. 2023.

Superconductivity from a melted insulator in Josephson junction arrays - Mukhopadhyay, Soham; Senior, Jorden L; Saez Mollejo, Jaime; Puglia, Denise; Zemlicka, Martin; Fink, Johannes M; Higginbotham, Andrew P (Nature Physics)
Arrays of Josephson junctions are governed by a competition between superconductivity and repulsive Coulomb interactions, and are expected to exhibit diverging low-temperature resistance when interactions exceed a critical level. Here we report a study of the transport and microwave response of Josephson arrays with interactions exceeding this level. Contrary to expectations, we observe that the array resistance drops dramatically as the temperature is decreased—reminiscent of superconducting behaviour—and then saturates at low temperature. Applying a magnetic field, we eventually observe a transition to a highly resistive regime. These observations can be understood within a theoretical picture that accounts for the effect of thermal fluctuations on the insulating phase. On the basis of the agreement between experiment and theory, we suggest that apparent superconductivity in our Josephson arrays arises from melting the zero-temperature insulator.
Keywords: General Physics and Astronomy

Tale of cAMP as a second messenger in auxin signaling and beyond - Qi, Linlin; Friml, Jiří (New Phytologist)
The 3′,5′-cyclic adenosine monophosphate (cAMP) is a versatile second messenger in many mammalian signaling pathways. However, its role in plants remains not well-recognized. Recent discovery of adenylate cyclase (AC) activity for transport inhibitor response 1/auxin-signaling F-box proteins (TIR1/AFB) auxin receptors and the demonstration of its importance for canonical auxin signaling put plant cAMP research back into spotlight. This insight briefly summarizes the well-established cAMP signaling pathways in mammalian cells and describes the turbulent and controversial history of plant cAMP research highlighting the major progress and the unresolved points. We also briefly review the current paradigm of auxin signaling to provide a background for the discussion on the AC activity of TIR1/AFB auxin receptors and its potential role in transcriptional auxin signaling as well as impact of these discoveries on plant cAMP research in general.

Control of tissue dimensions in the developing neural tube and somites - Minchington, Thomas; Rus, Stefanie; Kicheva, Anna (Current Opinion in Systems Biology)
Despite its fundamental importance for development, the question of how organs achieve their correct size and shape is poorly understood. This complex process requires coordination between the generation of cell mass and the morphogenetic mechanisms that sculpt tissues. These processes are regulated by morphogen signalling pathways and mechanical forces. Yet, in many systems, it is unclear how biochemical and mechanical signalling are quantitatively interpreted to determine the behaviours of individual cells and how they contribute to growth and morphogenesis at the tissue scale. In this review, we discuss the development of the vertebrate neural tube and somites as an example of the state of knowledge, as well as the challenges in understanding the mechanisms of tissue size control in vertebrate organogenesis. We highlight how the recent advances in stem cell differentiation and organoid approaches can be harnessed to provide new insights into this question.

Reaction-diffusion equations with transport noise and critical superlinear diffusion: Local well-posedness and positivity - Agresti, Antonio; Veraar, Mark (Journal of Differential Equations)
In this paper we consider a class of stochastic reaction-diffusion equations. We provide local well-posedness, regularity, blow-up criteria and positivity of solutions. The key novelties of this work are related to the use transport noise, critical spaces and the proof of higher order regularity of solutions – even in case of non-smooth initial data. Crucial tools are Lp(Lp)-theory, maximal regularity estimates and sharp blow-up criteria. We view the results of this paper as a general toolbox for establishing global well-posedness for a large class of reaction-diffusion systems of practical interest, of which many are completely open. In our follow-up work [8], the results of this paper are applied in the specific cases of the Lotka-Volterra equations and the Brusselator model.

Iterated medial triangle subdivision in surfaces of constant curvature - Brunck, Florestan R (Discrete and Computational Geometry)
Consider a geodesic triangle on a surface of constant curvature and subdivide it recursively into four triangles by joining the midpoints of its edges. We show the existence of a uniform δ>0 such that, at any step of the subdivision, all the triangle angles lie in the interval (δ,π−δ) . Additionally, we exhibit stabilising behaviours for both angles and lengths as this subdivision progresses.

Codes for the Z-channel - Polyanskii, Nikita; Zhang, Yihan (IEEE Transactions on Information Theory)
This paper is a collection of results on combinatorial properties of codes for the Z-channel . A Z-channel with error fraction τ takes as input a length- n binary codeword and injects in an adversarial manner up to n τ asymmetric errors, i.e., errors that only zero out bits but do not flip 0’s to 1’s. It is known that the largest ( L - 1)-list-decodable code for the Z-channel with error fraction τ has exponential size (in n ) if τ is less than a critical value that we call the ( L - 1)- list-decoding Plotkin point and has constant size if τ is larger than the threshold. The ( L -1)-list-decoding Plotkin point is known to be L -1/L-1 – L -L/ L-1 , which equals 1/4 for unique-decoding with L -1 = 1. In this paper, we derive various results for the size of the largest codes above and below the list-decoding Plotkin point. In particular, we show that the largest ( L -1)-list-decodable code ε-above the Plotkin point, for any given sufficiently small positive constant ε > 0, has size Θ L (ε -3/2 ) for any L - 1 ≥ 1. We also devise upper and lower bounds on the exponential size of codes below the list-decoding Plotkin point.

An energy decomposition theorem for matrices and related questions - Mohammadi, Ali; Pham, Thang; Wang, Yiting (Canadian Mathematical Bulletin)
Given A⊆GL2(Fq), we prove that there exist disjoint subsets B,C⊆A such that A=B⊔C and their additive and multiplicative energies satisfying max{E+(B),E×(C)}≪|A|3/M(|A|), where M(|A|)=min{q4/3/|A|1/3(log|A|)2/3,|A|4/5/q13/5(log|A|)27/10}. We also study some related questions on moderate expanders over matrix rings, namely, for A,B,C⊆GL2(Fq), we have |AB+C|, |(A+B)C|≫q4, whenever |A||B||C|≫q10+1/2. These improve earlier results due to Karabulut, Koh, Pham, Shen, and Vinh ([2019], Expanding phenomena over matrix rings, ForumMath., 31, 951–970).